Curable film composition, curable film, and cured product thereof
By combining hollow glass microspheres and rubber composite materials in the solderable film material, the problem of insufficient dielectric constant and thermal resistance of the solderable film material in the prior art is solved, and a high-performance solderable film suitable for high-density interconnected circuit board manufacturing is achieved.
Patent Information
- Application Number
- JP2024216302
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-02-17
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to develop solderable films with low dielectric constant, low dielectric loss tangent and excellent thermal resistance, and traditional pre-impregnated glass fiber materials have interlayer inhomogeneity and difficulty in machining when manufacturing high-density interconnected circuit boards.
Using a new solderable film material based on phenoxy/epoxy, combined with hollow glass microspheres and rubber composites, a film that can maintain shape and performance at high temperatures is prepared by optimizing formulation and processing technology.
The low dielectric constant and low dielectric loss tangent of solderable film are achieved, enhancing its thermal resistance and mechanical properties, making it suitable for manufacturing high-density interconnected circuit boards, especially multi-layer high-density interconnected circuit boards and ultra-high-density interconnected circuit boards.
Smart Images

Figure 2025038042000011 
Figure 2025038042000012 
Figure 2025038042000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for a curable film, a curable film made therewith, a cured product obtained by curing the curable film, and a method for making the curable film. The curable film is thin, has a very light weight and excellent processability. The cured product has desirable dielectric and thermomechanical properties suitable as a circuit material, for example, for making printed circuit boards (PCBs). The curable film can thus be used to replace prepregs with advantageous results. The present invention also relates to PCB dielectric layers made from the curable film, especially for multilayer PCBs and HDI PCBs. [Background technology]
[0002] For example, the need to support high data rates for high speed computers and the demand for small and / or lightweight electronic devices such as mobile devices, IoT devices, autonomous systems (LiDAR, radar, and cameras) for self-driving cars and drones, and electronic components for medical and military communication equipment, 5G applications, etc. have led to the search for new insulators for circuit materials.
[0003] Printed circuit boards (PCBs) are used in almost every electronic product today. A basic PCB includes a flat sheet of insulating material (the dielectric layer) and a layer of copper foil laminated to the substrate. PCBs can be single-sided (one copper layer), double-sided (two copper layers), or multi-layered, allowing for high component density. Multi-layer PCBs, which became more common in the 1990s, are complex composite structures that typically include a series of layers of reinforced resin and copper foil. Conductors on different layers can be connected by "vias" or plated through holes. High density interconnect (HDI) technology allows for even denser designs in a given area on a PCB. Multi-layer HDI PCBs are not only more compact, but also have fewer layers, lighter weight, and smaller vias, pads, copper traces, and spaces. In addition, by shortening the distance between devices and trace spaces, HDI PCBs allow for more transistors for better performance in electronics while consuming less power. Signal integrity is also improved due to the shorter distance connections and lower power requirements. The result is more compact and smaller PCBs with improved performance.
[0004] There are three common HDI structures. The first structure is the 1+n+1 structure, which has one layer built up on each side of a core assembly containing n layers. Typically, the minimum value of n is 2. The second structure is the i+n+i structure, where i is 2 or more. This means a build of i layers on each side of an n-layer core assembly, where i is 2 or more. An exemplary i+n+i HDI PCB is shown in FIG. 1A, where the center is a 6-layer (i.e., n=6) glass-reinforced core and the outer 4 (i.e., i=4) layers are glass-reinforced prepreg-based layers. The third is the anylayer HDI PCB, where all layers can be interconnected using copper-filled vias. Anylayer HDI PCBs are commonly used in mobile devices. An exemplary anylayer HDI PCB configuration is shown in FIG. 1B, where the center core is a double-sided glass-reinforced laminate and the outer layers are glass-reinforced prepreg-based layers.
[0005] Driven by ever-increasing demands for component miniaturization, mobile computing, and 5G applications, HDI PCBs utilize the latest technology to further reduce the area while increasing the functionality of the circuit board. HDI PCBs are currently widely used in applications that demand smaller sized circuit boards, such as mobile phones, touch screen devices, laptop computers, digital cameras, 5G network communications, autonomous systems in the automotive and aerospace industries, medical devices, and military applications such as avionics and smart munitions. To save space, HDI PCBs require the use of thin layers of dielectric materials that sacrifice little of the desired thermo-mechanical and electrical properties.
[0006] PCB manufacturing processes that join conductive and insulating materials require thermal runs over a large temperature range, on the order of 250-300°C. The introduction of interconnect conductors, including vias or microvias, also requires certain processes that are thermo-mechanically challenging. Almost all PCBs require that the conductive layers be made from copper metal conductive sheets and traces. This introduces stringent requirements on the properties of dielectric base materials that can be used to produce PCBs that contain copper conductive elements. Because conductive copper materials and dielectric materials may have dissimilar thermo-mechanical properties, PCB manufacturing has stringent requirements on the thermo-mechanical properties of the construction materials that are considered suitable for use as dielectric base materials. Thus, only a very small number of dielectric base materials with specific thermo-mechanical properties can be used to manufacture PCBs. If the materials used in the dielectric layers do not fall within an accepted range of thermo-mechanical properties that are compatible with the copper conductive layers, PCB failure will occur. The selection of dielectric materials with acceptable thermo-mechanical properties is thus an important factor to consider in the field of PCB material design. In the past, the need to match the thermomechanical properties of copper has led to the prioritization of thermomechanical design rules at the expense of optimized electrical properties in dielectric-based materials. In general, a suitable dielectric material must have a low tendency to expand when heated and be relatively rigid when exposed to mechanical forces. These properties of low thermal expansion and high rigidity are believed to prevent excessive movement relative to the copper conductor layers during processing and to prevent excessive strain on the interconnects during PCB cycle life. However, the limitations placed on the range of acceptable thermomechanical properties required for compatibility with copper conductive layers have limited the development of new dielectric materials with optimized electrical properties that can be adapted to existing PCB designs.
[0007] Many dielectric materials used to make PCBs incorporate fiber reinforcement into the thermosetting resin system. The reinforcement usually takes the form of woven or nonwoven glass fiber. Prepreg is a technical term used to describe woven or nonwoven fabrics impregnated with a thermosetting resin composition. The terms A-stage, B-stage, and C-stage are used to describe prepregs in the uncured, partially cured, and fully cured states, respectively. Prepregs are the workhorse of the PCB industry, and there are numerous types of fiberglass cloth used to make prepregs for PCB base materials, with different glass weaves, thicknesses, and dielectric constants. The majority of prepreg PCB base materials use glass fiber, although other fiber reinforcements may be used. A-stage or B-stage prepregs may be stacked to meet the required thickness, and metal foils, such as copper foil, are stacked on one or both sides. The resulting assembly is then heated and pressed (often called lamination) to form a metal clad laminate (e.g., single clad or double clad). During the lamination process, the thermosetting resin composition of the prepreg adheres to the metal foil and cures to form a copper clad insulating layer. The C-stage prepreg or laminate is commonly referred to in the art as a "core." The core may be single or double clad with copper, and the copper may be etched to form a pattern for the circuitry.
[0008] Traditional PCB manufacturing processes typically involve building multi-layer PCBs in a single lamination process where cores and prepregs are stacked alternately. This contrasts with HDI PCB manufacturing processes where layers are added sequentially, i.e. it is a build-up process, requiring a new lamination cycle for each build-up. Prepregs are traditionally used for the build-up layers.
[0009] Typical thermosetting resins include epoxy resins, polyester resins, cyanate ester resins, phenol formaldehyde resins, BT resins, polyphenylene ether resins, and their hybrids. Additives such as flame retardants, hardeners, fillers, UV absorbers, coupling agents, tougheners, tack modifiers, antioxidants, and thixotropic agents can be introduced into the resin system to adjust the dielectric and physical properties of the polymer dielectric composite material. Generally, expensive products in the industry try to balance the best electrical properties with the least expansion, which can lead to manufacturing-related problems such as brittleness and reliability issues.
[0010] Conventional cured prepreg is a composite formed with glass fibers, and therefore it is inhomogeneous and anisotropic. Many properties are affected, such as the dielectric properties in x, y, and z directions, the coefficient of thermal expansion (CTE), and Young's modulus (also known as tensile modulus). The problem of anisotropy and non-uniform dielectric properties causes "skew" in PCBs. Mechanical processes such as drilling (either mechanical or laser) and removing debris from holes are difficult. Problems such as excessive heat build-up, lower productivity, and lower reliability are also identified. In addition, glass cloth thickness is a barrier to achieving 25 μm or less in dielectric layer thickness for PCBs, thereby hindering the miniaturization process. The lack of availability of thin glass fibers combined with their relatively high dielectric constant is a special problem for the ever-increasing miniaturization of PCBs.
[0011] Particulate mineral or ceramic fillers can be added to the prepreg composition to adjust the dielectric and physical properties. Hollow glass microspheres are especially used to lower the dielectric constant. Before use, the glass spheres are usually subjected to a surface treatment to improve the wetting of the spheres by the polymer matrix and / or to improve bonding for coupling reactions. U.S. Pat. No. 9,258,892 (Crossley) discloses the use of hollow glass microspheres surface-treated with an alkaline solution to obtain a dielectric substrate layer having a low dielectric constant and low dielectric loss tangent. According to Crossley, compared to hollow glass microspheres subjected to a conventional surface treatment using an acid solution, the hollow glass microspheres treated with an alkaline solution achieved improved results (i.e., lower dielectric constant and lower dielectric loss tangent). Despite the use of a different solution, Crossley calls for washing the glass spheres with an alkaline solution to modify the surface properties of the particles. In addition, Crossley does not teach the formation of a film that can be handled and processed without a substrate. In fact, the dielectric formulations described in Crossley have been shown to be suitable for prepregs, as illustrated by the examples described therein.
[0012] The majority of multi-layer PCBs are manufactured using prepregs. Thus, there are various known techniques for certain thermosetting resin compositions that are considered beneficial for use in prepregs. The general trend toward low expansion prepregs is realized by using thermosetting compositions with high glass transition temperatures (Tg). However, such compositions tend to have brittle or solid-like behavior and thus would be expected to have poor film-forming capabilities and require a support such as fiberglass to be useful in the manufacture of PCBs. Such thermosetting compositions are likely not even suitable for making films that can be transferred from one substrate to another, i.e., Type-3 curable films as defined herein (see below). Even if a selection of thermosetting compositions were capable of forming Type-3 films when coated on copper (often referred to as resin-coated copper or RCC), such RCCs would have drawbacks in the manufacture of PCBs, including poor dielectric spacing control. Thus, there is a need for thermosetting compositions that can form better films that are more suitable for use in the manufacture of PCBs, including, for example, as PCB base materials for core and / or prepreg replacement in the manufacture of conventional and HDI PCBs.
[0013] Ajinomoto's build-up film (ABF), based on a phenoxy / epoxy thermosetting composition, is a curable film used in the electronics industry that can be handled without a supporting substrate and is a common material for IC packaging, as described, for example, in U.S. Pat. No. 6,805,958 (Nakamura et al.). However, it is used very little, if at all, in the manufacture of PCBs. U.S. Pat. No. 11,359,062 (Amra et al.) describes a curable film based on a PHAE / epoxy thermosetting composition that has a dielectric constant similar to ABF but a lower cured Tg. However, both examples have limitations of a dielectric constant (Dk) of more than 3 at 10 GHz and relatively high dielectric losses of more than 0.005, 0.010, or even 0.015.
[0014] The successful development of a better curable film that can replace the conventional prepreg and / or core for PCB manufacturing could enable PCBs with improved reliability, especially if the material based on the film thus cured in the PCB has a low modulus and low Tg as described in U.S. Patent Application No. 17 / 700,928, the entire disclosure of which is incorporated herein by reference. Furthermore, in recent years, the signal band of information communication devices such as PHS or mobile phones and the CPU clock time of computers have reached the GHz band, and higher frequencies are used more and more frequently. The dielectric loss of an electric signal is proportional to the product of the square root of the relative dielectric constant of the insulator forming the circuit, its dielectric loss tangent, and the frequency of the signal used. Therefore, the higher the frequency of the signal used, the greater the dielectric loss. The dielectric loss attenuates the electric signal and impairs the reliability of the signal. In order to suppress such damage, it is required to select a material with a small relative dielectric constant and a small dielectric loss tangent as the insulator.
[0015] U.S. Patent No. 7,541,408 (Ohno et al.) describes an adhesive film with a very low dielectric constant for use as a bonding sheet or coverlay in flexible printed circuits (FPCs). Ohno's film contains divinyl polyphenylene ether with a molecular weight of 70,000 to 300,000. FPCs generally have a structure in which a circuit pattern is formed on a copper foil laminated onto a plastic film having heat resistance and insulating properties, such as polyimide, and the circuit pattern is filled with a thermosetting insulating resin and then covered with another heat-resistant film. A film in which the uncured circuit pattern-filled resin and the heat-resistant film are previously integrated is called a coverlay film, and various types of coverlay films have been proposed so far. In addition, FPCs are widely made to have a multilayer structure for high-density mounting, and a bonding sheet obtained by processing a thermosetting adhesive into a thin sheet has been used to form the multilayer structure. In FPCs prepared by a method using a flexible copper clad laminate (FCCL) obtained by laminating copper foil on a polyimide film or the like, a coverlay film, and a bonding sheet, the insulating properties between copper foil layers are guaranteed through the polyimide film. However, in response to recent demands for high functionality of FPCs, particularly for thinning, a method has been proposed in which the insulating properties between copper foil layers are guaranteed by using a thermosetting adhesive used in a coverlay film or a bonding sheet without using a polyimide film or the like. In this method, a flexible resin-coated copper (FRCC) in which an uncured thermosetting adhesive layer and a copper foil are integrated is used. The base layer for PCB applications requires a filler. However, it is known that the incorporation of a filler has a detrimental effect on film formation or film handling properties. Ohno emphasizes the difficulty of creating an ideal curable film, especially a type-5 curable film as defined herein (see below), even when no filler is present in the curable film.
[0016] Thus, with smaller substrate features and higher frequency signals, there is a need for curable films that have a low dielectric constant, are easy to process, can form thinner dielectric layers than currently available, and have excellent thermo-mechanical properties. Summary of the Invention
[0017] In view of the above problems, it is an object of the present invention to provide a composition for a curable film that is thin, easy to process, and has excellent dielectric and thermomechanical properties when cured. Another object is to provide a curable film suitable for replacing prepregs in PCBs, especially multi-layer PCBs and HDI PCBs. In particular, it is an object of the present invention to provide a curable film that is releasable and transferable, has no or low tackiness, can be handled in a free-standing state, and can be used to create a cured body with low dielectric constant, low dielectric loss tangent, and excellent heat resistance. These and other objects have been achieved by the present invention.
[0018] The present inventors have developed in the present invention a novel class of curable films that can be used as dielectric base materials with an entirely new range of thermomechanical properties that were previously taught to be unacceptable for use as PCB base materials. The curable films of the present invention are relatively flexible, yet can be easily incorporated to create rigid multilayer PCBs. Despite decades of teaching that dielectric base materials with both high CTE and low tensile modulus cannot be used in PCBs, the present inventors have surprisingly found that the materials of the present invention are compatible for use with copper conductive layers in PCBs. In fact, the curable films of the present invention can be used to manufacture reliable multilayer HDI PCBs with no failure during thermal processing, can be used in multilayer HDI PCB designs with no failure of conductive interconnects during thermal excursions of hundreds of degrees Celsius, and can be used over long cycle lives without via or microvia fracture. Most surprisingly, the dielectric materials of the present invention have been demonstrated to enable the fabrication of reliable multilayer HDI PCB structures of at least 14 layers that contain stacked microvias directly above buried vias that cannot be created with any other currently available dielectric materials. Thus, the novel dielectric-based materials of the present invention allow previously unattainable design elements to be reliably incorporated into multi-layer HDI PCB structures that can withstand manufacturing and thermal cycling without failure of the interconnects between conductive layers, as has never before been possible.
[0019] In particular, the inventors have surprisingly discovered that when a rubber composition containing one or more diene rubbers is mixed with hollow glass microspheres of the correct particle size or mixed with maleimide resin and fillers, such as silica and glass microspheres, a cured film (particularly a Type-5 cured film as defined herein below) that is homogeneous, isotropic, easy to process, and free of cracks or voids even at high filler loadings can be obtained. Such cured films are ideal for creating dielectric layers with desirable thermomechanical and dielectric properties, especially for multilayer PCBs and HDI PCBs, as they enable the manufacture of reliable and durable PCBs by reducing the incidence of PCB failure. The dielectric materials of the present invention are also useful as semiconductor interconnect (IC) packages, energy storage materials, high performance composites (e.g., reinforced plastics) for structural or non-structural applications (e.g., automotive, aerospace, and decorative applications), dielectric adhesives (used in the manufacture of or for bonding electrical products), and other applications where the ability to precisely control electrical, mechanical, and thermal properties is important.
[0020] According to an embodiment of the present invention, a curable film composition or a curable film is provided that contains hollow glass microspheres (HGM) having a specified particle size and a rubber composition. The rubber composition preferably contains one or more diene-based rubbers. In particular, the curable film contains, as component (A), 2-65 wt % HGM and, as component (B), a rubber composition that preferably contains a diene-based rubber having a weight average molecular weight of at least 60,000. The HGM can be used as is. In particular, the present invention surprisingly shows that, contrary to the teachings of the prior art and contrary to the knowledge of those skilled in the art, pre-cleaning of the HGM using either an acid solution or an alkaline solution is not required to achieve the desired electronic properties (e.g., low Dk and low Df). Optional components contained in the curable film composition or the curable film include other non-elastomeric polymers or oligomers, such as maleimide resins, hydrocarbyl thermoplastic polymers, and styrene maleic anhydride resins. According to an embodiment of the present invention, the curable film composition or the curable film contains one or more fillers in addition to the HGM.
[0021] According to another embodiment of the present invention, there is provided a curable film composition or a curable film comprising a filler, a rubber composition, and a maleimide resin. In this embodiment, the maleimide resin is a necessary component along with the filler and the rubber composition. The rubber composition preferably comprises one or more diene-based rubbers. In particular, the curable film composition or the curable film comprises, as component (A), 10-80 wt. % of a filler, e.g., silica and HGM, as component (B), a rubber composition comprising a diene-based rubber, preferably having a weight average molecular weight of at least 60,000, as component (C), and a maleimide resin having a solubility in toluene of at least 5 g / 100 ml at ambient temperature.
[0022] The diene-based rubber can be one or more selected from the group consisting of styrene-butadiene rubber (SBR), other styrenic rubbers such as styrenic block copolymers (SBC), polybutadiene (PBD), polyisoprene (IR), butyl rubber (BR), ethylene propylene rubber (EPR), ethylene propylene diene monomer rubber (EPDM) which may or may not be partially or fully hydrogenated, and hydrogenated styrenic block copolymers (HSBC).
[0023] The curable film composition of the present invention may or may not include a woven or nonwoven fabric. The curable film of the present invention may or may not include a reinforcing layer. In some embodiments, the curable film composition of the present invention may be used to impregnate a woven or nonwoven fabric, which may be anisotropic, quasi-isotropic, or substantially isotropic.
[0024] According to an embodiment of the present invention, the rubber composition of the curable film composition (i.e., component (B)) further comprises one or more liquid rubbers and / or low molecular weight diene-based rubbers. According to an embodiment of the present invention, the rubber composition (B) further comprises a polyphenylene ether or a polyphenylene ether resin. According to an embodiment of the present invention, the rubber composition (B) further comprises one or more radical initiators and / or curing agents.
[0025] According to an embodiment of the present invention, the curable film optionally includes a flame retardant. According to an embodiment of the present invention, the curable film optionally includes one or more adjuvants, such as an adhesion promoter, a silane coupling agent, and an antioxidant.
[0026] According to an embodiment of the present invention, there is further provided a method for preparing a curable film by processing the curable film composition into the form of a film. According to an embodiment of the present invention, the curable film can be provided on a carrier substrate, thus obtaining a film assembly including the curable film and the carrier film. The curable film can be released from the carrier film and / or transferred from the carrier film to another substrate, while still having sufficient integrity to be handled in a self-supporting form. The carrier substrate may be disposable.
[0027] According to an embodiment of the present invention, the curable film is incorporated into the assembly and cured to obtain a cured body. In another embodiment, the curable film is obtained by curing a curable film clad on one or both sides with copper to obtain a core. The core does not include glass fiber reinforcement and is therefore a skew-free core. In another embodiment, the curable film replaces traditional prepregs in the creation of circuit laminates. In another preferred embodiment, a dielectric layer is obtained from the curable film. The dielectric layer can be used in PCBs.
[0028] The above paragraphs have been provided by way of general introduction and are not intended to limit the scope of the claims which follow. The described embodiments, together with further advantages, will be best understood by reference to the following detailed description taken in conjunction with the accompanying drawings, in which: [Brief description of the drawings]
[0029] [Figure 1A] 1 shows an exemplary i+n+i HDI PCB with a central glass reinforced n-layer core and outer i-layers that are prepreg-based layers. [Figure 1B] 1 shows an exemplary anylayer HDI PCB with a double-sided glass reinforced core in the middle and prepreg-based outer layers. [Diagram 2]FIG. 1 shows a 20-layer PCB stackup structure used in the examples described herein, in which Type-5 curable film is used as a bonding layer instead of a prepreg layer. [Diagram 3] FIG. 3 shows an optical cross section after thermal stress of a cross section of a 20-layer PCB having a structure as shown in FIG. 2, in which the inventive Type-5 curable film E9 is used as a bonding layer. [Figure 4] FIG. 3 shows an optical cross section after thermal stress of a cross section of a 20-layer PCB having a structure as shown in FIG. 2, in which comparative curable film C1 is used as a bonding layer. [Diagram 5] Shown is a 4+6+4 HDI PCB stackup structure where the center layer is a glass reinforced prepreg based layer and the four buildup layers are from the inventive Type-5 curable film E9. [Figure 6] 6 shows an optical cross section of the 4+6+4 HDI PCB of FIG. 5 after 100 thermal stress cycles up to 160°C. [Figure 7A] 6 shows the change in electrical resistance of the 4+6+4 HDI PCB of Figure 5 during reflow measured according to IPC-TM-650, method 2.6.7.2. [Figure 7B] FIG. 6 shows the change in electrical resistance of the 4+6+4 HDI PCB of FIG. 5 during thermal shock cycling measured according to IPC-TM-650, method 2.6.7.2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] As used herein, the terms "invention," "the invention," "the present invention," and the like, when they appear both in the headings and in the text, refer to the particular embodiment that immediately follows, and are not intended to be generally limiting, nor are they intended to be general limitations on any particular advances in the art that are described herein.
[0031] When an amount, concentration, or other value or parameter is given herein as a range and / or as a list of values, this should be understood as specifically disclosing all ranges formed from any pair of upper and lower limits, including the endpoints, and including all integers and fractions within the range, whether or not all such ranges, integers, and fractions are separately disclosed. For example, the range of 1 to 10 includes and discloses 3 and 5.5. It is not intended that the scope of the invention be limited to the specific values recited when defining a range.
[0032] The use of "a" or "an" to describe various elements and components is for the purpose of giving a general sense of the present disclosure, and such terms should be construed to include one or more elements and components unless a different intention is apparent.
[0033] The terms "about" and "approximately" as used herein mean approximately the same as the stated amount or value and should be understood to encompass ±5% of the specified amount or value. The term "substantially" as used herein means all, or nearly all, or the majority, as understood by those skilled in the art, unless otherwise defined. It is intended to allow for some reasonable variation from 100%, which in practice would normally occur, for example, in an industrial or commercial scale situation.
[0034] As used herein, "prepreg" means a woven or nonwoven fabric impregnated with a thermosetting composition.
[0035] As used herein, "ambient temperature" or "room temperature" refers to a temperature range of 15 to 25°C.
[0036] In this disclosure, different curable films are divided into five types depending on their appearance, homogeneity, and processability:
[0037] A "Type-1 curable film" (sometimes abbreviated to "Type-1 film") refers to a coating or covering on a supporting substrate, the film having a non-uniform covering and non-uniform morphology, for example, as characterized by different thicknesses and the presence of defects such as voids, voids, lumps, and cracks. A composition can form a Type-1 film as long as it can be spread on a supporting substrate, even if it has a high viscosity.
[0038] "Type-2 Curable Film" (sometimes abbreviated as "Type-2 Film") refers to a coating or covering on a supporting substrate, which film is substantially uniform and homogeneous, and free of obvious defects such as voids, voids, lumps, and cracks.
[0039] A "Type-3 Curable Film" (sometimes abbreviated as "Type-3 Film") refers to a coating or covering having a free surface and a contact surface for contacting a supporting substrate, wherein the film is substantially uniform and homogeneous, free of obvious defects such as voids, voids, lumps, and cracks, and is transferable or releasable from an original supporting substrate to a new supporting substrate by contacting the new supporting substrate to the free surface of the film. Pressure sensitive adhesives and iron-on transfers, such as those used on t-shirts and fabrics, are examples of Type-3 films.
[0040] A "Type-4 curable film" (sometimes abbreviated to "Type-4 film") refers to a coating or covering on a support substrate, the film being substantially uniform and homogeneous, free of obvious defects such as voids, gaps, lumps, and cracks, and capable of being peeled off from the support substrate in its entirety in one piece. Type-4 films differ from Type-3 films in that Type-4 films do not require another substrate to remove the film from its original support substrate, and can exist at least temporarily without a substrate. Although Type-4 films can exist at least temporarily without a substrate after being peeled off, the films cannot be processed without a substrate. As such, Type-4 films must be transferred to a new substrate for manipulation after being peeled off from its original support substrate. Ajinomoto Build-Up Film (ABF), described in U.S. Pat. No. 6,805,958 (Nakamura et al.), is an example of a Type-4 film.
[0041] A "Type-5 curable film" (sometimes abbreviated to "Type-5 film") refers to a coating or covering on a supporting substrate, the film being substantially uniform and homogeneous, free of obvious defects such as voids, voids, lumps, and cracks, and peelable from the supporting substrate in its entirety and in one piece so that it can be handled without a substrate. Thus, Type-5 films differ from Type-4 films in that Type-5 films can be handled, processed, or manipulated without support and without a substrate. Type-5 films are essentially free-standing films without being combined with a base material (e.g., glass cloth, glass, or aramid nonwoven) or supported by a substrate. Rogers 2929 Bondply is an example of a Type-5 film. Films based on PHAE / epoxy thermosetting compositions described in U.S. Pat. No. 11,359,062 (Amra et al.) are another example of a Type-5 film.
[0042] The inventive film compositions described herein are used to form curable films that are Type-3, Type-4, and Type-5 films, preferably Type-4 and Type-5 films, and more preferably Type-5 films. The curable films can be used to replace prepregs and / or cores in the manufacture of PCBs and to enable the manufacture of high reliability microvias. The curable film has low insertion loss because the thus cured film as an insulating layer has a low dissipation factor (Df) (e.g., <0.005, <0.004, <0.003, <0.002, <0.0015, or <0.0012, or about 0.001, or about 0.0009, measured at 10 GHz), or a combination of a low Df and a moderately low Dk (e.g., 2.8-3.1, measured at 10 GHz), low Dk (e.g., 2.5-2.8, measured at 10 GHz), very low Dk (e.g., 2.2-2.5, measured at 10 GHz), or extremely low Dk (e.g., 1.8-2.2, measured at 10 GHz).
[0043] In a preferred embodiment of the present invention, the curable film composition or curable film comprises hollow glass microspheres as component (A) and a rubber composition containing one or more diene-based rubbers as component (B). The content of the hollow glass microspheres in the curable film ranges from about 2% to about 65% by weight, based on the total weight of the curable film. The curable film may further contain particulate fillers other than hollow glass microspheres, and the total content of the fillers in the curable film may range from about 2% to about 80% by weight, based on the total weight of the curable film. The diene-based rubber preferably has a weight average molecular weight of at least 60,000. The rubber composition (B) may further contain an initiator and / or a curing agent. The rubber composition (B) may further contain other components such as liquid rubber, polyphenylene ether, and low molecular weight diene rubber. The curable film may further contain other non-elastomeric polymers, flame retardants, and other auxiliary agents.
[0044] In another preferred embodiment of the present invention, the curable film composition or curable film includes, as component (A), a filler such as silica and hollow glass microspheres, as component (B), a rubber composition containing one or more diene rubbers, and as component (C), a maleimide resin. The content of the filler ranges from about 10% to about 80% by weight in the curable film. The diene rubber preferably has a weight average molecular weight of at least 60,000. The maleimide resin has a solubility in toluene of at least 5 g / 100 ml at ambient temperature and preferably has a weight average molecular weight of at least 1,000. The rubber composition (B) of the curable film may further include an initiator and / or a curing agent, and other components, such as liquid rubber, polyphenylene ether, and low molecular weight diene rubber. The curable film may further include other non-elastomeric polymers, flame retardants, and other auxiliary agents.
[0045] According to an embodiment of the present invention, the curable film has a thickness of about 10 μm to about 250 μm. In one embodiment, the curable films can be stacked together to provide greater thicknesses, and the stacked films can be cured with heat and pressure to a target layer thickness that can exceed 250 μm.
[0046] [Rubber composition] <Diene rubber> In an embodiment of the present invention, diene rubber is an essential component of the curable film. IUPAC defines an elastomer as a polymer that exhibits rubber-like elasticity. That is, diene rubber is an elastomer, which is a polymer that has viscoelasticity and generally low Young's modulus and high elongation when compared to other polymers such as engineering thermoplastics (e.g., nylon, PET). The inventors of the present invention have found that elastomer is a key component to imparting excellent film forming ability, good film handling properties, and the ability to produce, for example, type-5 films even at high filler (e.g., HGM, silica, and other particulate fillers) loadings. For example, it has been found that compositions containing elastomer in amounts of 10 wt. % or less in addition to other ingredients can be used to make type-5 curable films, while compositions containing all other ingredients except elastomer nevertheless cannot be used to make even type-1 or type-2 films. The inventors have also found that when properly formulated, the elastomers also provide good heat resistance and excellent electrical properties in the cured product, enabling the use of the elastomers as components in prepreg replacements for PCB manufacture.
[0047] The mechanism is unclear. However, without wishing to be bound by theory, the inventors believe that the fact that elastomers are amorphous polymers at ambient temperatures of 15-25°C due to their low glass transition temperature (Tg) is a key factor. It has been discovered that a wide range of elastomeric materials may be used. For purposes herein, "elastomeric material(s)," "elastomer(s)," and "rubber(s)" are synonymous and include natural rubber, synthetic rubber, diene-based rubber (including diene rubber), and thermoplastic elastomers. The elastomeric materials used in the curable film compositions described herein can also be bio-derived or bio-based, rather than petrochemically derived. That is, the chemical feedstocks used for the synthesis of the rubber can be derived, in whole or in part, from bio-renewable resources.
[0048] Diene-based rubbers are one of the preferred choices for the rubber composition (B) of the curable film of the present invention. Diene-based rubbers are typically amorphous polymers with a Tg ranging between 170K and 250K (-100°C to -25°C) and contain unsaturated sites that make them curable (i.e., crosslinkable) or co-curable with other components that may be incorporated into the curable film composition. Preferably, the diene-based rubber is at least one selected from the group consisting of styrene-butadiene rubber (SBR), other styrenic rubbers such as styrenic block copolymers (SBC), polybutadiene (PBD), polyisoprene (IR), butyl rubber (BR), ethylene propylene rubber (EPR), and ethylene propylene diene monomer rubber (EPDM). The rubber may be partially or fully hydrogenated. For example, hydrogenated styrene block copolymers (HSBC) can be used. It should be mentioned that other widely available rubbers such as nitrile-butadiene rubber (NBR) and polychloroprene (CR) can be used to make Type-5 films, but their use is limited to PCB-related applications due to undesirable electrical and / or heat resistance properties of the cured material.
[0049] In some embodiments, styrene-based elastomers are particularly preferred and may include random copolymers and block copolymers. In some embodiments, such suitable elastomers include elastomeric block copolymers that include a block (A) derived from an alkenyl aromatic compound and a block (B) derived from a conjugated diene. The arrangement of blocks (A) and (B) includes linear structures and graft structures, including radial teleblock structures with branched chains. Examples of linear structures include diblock (AB), triblock (ABA or BAB), tetrablock (ABAB), and pentablock (ABABA or BABAB) structures, as well as linear structures that include a total of 6 or more blocks of A and B.
[0050] In some embodiments, the compound used to provide block (A) is an alkenyl aromatic compound as disclosed in U.S. Pat. No. 9,265,160 (Paul et al.). In some embodiments, the alkenyl aromatic compound is styrene.
[0051] In some embodiments, the conjugated dienes used to provide block (B) include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), sesquiterpenes (e.g., farnesene-based), 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene, in particular 1,3-butadiene and isoprene. Combinations of conjugated dienes may be used. The dienes may be derived from biorenewable resources. Block (B) derived from conjugated dienes is optionally partially or fully hydrogenated.
[0052] Exemplary block copolymers comprising a block (A) derived from an alkenyl aromatic compound and a block (B) derived from a conjugated diene include styrene-butadiene diblock copolymer (SB), styrene-butadiene-styrene triblock copolymer (SBS), styrene-isoprene diblock copolymer (SI), styrene-isoprene-styrene triblock copolymer (SIS), styrene-(ethylene-butylene)-styrene triblock copolymer (SEBS), styrene-(ethylene-propylene) copolymer (SEP), styrene-(ethylene-propylene)-styrene triblock copolymer (SEPS), styrene-ethylene-(ethylene-propylene) triblock copolymer (SEEP), styrene-(ethylene-butylene) diblock copolymer (SEB), and hydrogenated styrene farnesene copolymer (HSFC).
[0053] In some embodiments, the rubber may be selected from elastomers rich in vinyl bonds. The vinyl-containing elastomer may have a high vinyl content (e.g., more than 70%, 80%, or 90% of suitable structural units having vinyl groups), a moderate vinyl content (e.g., between 30% and 70% of suitable structural units having vinyl groups), or a low vinyl content (e.g., less than 30% of suitable structural units having vinyl groups).
[0054] In some embodiments, the rubber may be modified or post-modified with other reactive groups that may aid in compatibilization of components in the curable film or modify the properties of the film after curing, such as promoting adhesion to the substrate. Examples of modifications include rubber midblocks or other blocks grafted with maleic anhydride, and silicon modified blocks. In some embodiments, the rubber may be substantially free of alkenyl or vinyl groups, for example by substantial hydrogenation, and yet the cured body of the curable film containing the rubber is still suitable as an interlayer of a PCB, since the cured body does not exhibit measurable creep.
[0055] Illustrative, but non-limiting, examples of commercially available elastomers that may be used as the diene-based rubber of the rubber composition (B) of the present invention include those sold under the trade names Kraton®, Stereon®, Septon®, Hybrar®, K-Resin®, Styroflex®, Styrolux®, Royalene®, Royaledge®, Diene®, and Royalthrem®.
[0056] Although not particularly limited, the molecular weight of the diene rubber is typically >10,000, preferably >50,000 or >60,000, and more preferably >100,000 or >200,000. The rubber composition (B) of the curable film composition can contain one diene rubber or two or more diene rubbers that can be of different molecular weights.
[0057] The melt flow index of the diene rubber can vary and is not particularly limited as long as other factors such as the total filler loading, other non-elastomeric components present in the rubber composition (B), the target rheology for the PCB press lamination process, and the choice of radical initiator in the rubber composition (B) are taken into consideration. In addition, to replace the prepreg layer, the curable film may be required to have a suitable rheology to flow and fill the copper traces of the layer below. Under such circumstances, diene-based rubbers with higher melt flow rates are typically more desirable. For example, the melt flow index at 190-200°C in the range of 2-10 kg is preferably >1, >2, >5, >10, >15, or >20. In some embodiments, the melt flow index at 190-200°C in the range of 2-10 kg is about 1-200, 1-3, 3-50, 5-10, 10-20, 20-100, or 20-200.
[0058] In some embodiments, the amount of one or more diene rubbers contained in the rubber composition (B) of the curable film ranges from about 55% to about 100% by weight (e.g., 99%, 90%, 80%, 70%, 65%, 60%, and 55% by weight) based on the total weight of the rubber composition (B). In some embodiments, the diene rubber(s) are present in the rubber composition (B) in an amount of about 15% to about 50% by weight (e.g., 50%, 45%, 40%, 35%, 30%, 25%, 20%, and 15% by weight) based on the total weight of the rubber composition (B). In some embodiments, the diene rubber(s) may be present in the curable film composition in an amount as little as about 5 to 15% by weight (e.g., 5%, 8%, 10%, and 13% by weight) based on the total weight of the curable film. In some embodiments, the diene rubber(s) may be present in the curable film composition in an amount ranging from about 20% to 90% by weight (e.g., 20%, 22%, 30%, 36%, 46%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, and 90% by weight), based on the total weight of the curable film.
[0059] <Initiator, hardener> The films of the present invention are curable, that is, components within the film may react and / or crosslink to "set" the film so that the cured material does not exhibit deleterious creep behavior. In some embodiments, the curable films may be cured at temperatures of about 80°C to about 250°C, and preferably about 120°C to about 250°C, and more preferably about 140°C to about 220°C. In some embodiments, the films have a long working time at or below room temperature, thereby having sufficient "shelf life" that they can be stored and then used in the field (e.g., cured when they are used to manufacture PCBs) weeks, months, or years after their manufacture. It is not a requirement of the present invention that the curable films be completely crosslinked under the conditions of curing for use. What is important is the desired rheological behavior of the cured body, e.g., there should be virtually no creep when the cured film is used as an insulating layer in a PCB. Since many diene rubbers have the potential to be thermally cured without any external cure accelerator or curing agent, in some embodiments of the invention, the curable film composition does not include a curing agent, especially when the diene rubber of rubber composition (B) is vinyl-rich. However, in preferred embodiments, the rubber composition (B) of the curable film includes a radical initiator and / or curing agent so that the cure behavior of the film is appropriate, e.g., suitable for use in lamination processes typical of PCB manufacturing. One important factor to consider in selecting the correct radical initiator and / or curing agent is that they do not measurably activate the reaction during drying, especially when the curable film composition is prepared with a solvent.
[0060] The rubber composition (B) may include a free radical source that may be thermally activated, for example, as an initiator or curing agent. Examples of free radical sources that may be thermally activated include peroxides, azo compounds (e.g., α,α'-azobis(isobutyronitrile)), redox initiators (e.g., a combination of a peroxide such as H2O2 with a ferrous salt), and azides (e.g., acetyl azide). The free radical source may include at least one of a peroxide initiator, an azo initiator, a carbon-carbon initiator, a persulfate initiator, a hydrazine initiator, a hydrazide initiator, and a halogen initiator. The free radical source may include at least one of 2,3-dimethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, and 1,4-diisopropylbenzene. The free radical source may include at least one of an organic peroxide, such as dicumyl peroxide, t-butyl peroxybenzoate, α,α'-di-t-butylperoxy, diisopropylbenzene, and 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne. The free radical source may include a peroxide having a decomposition temperature of at least 50° C. Examples of peroxides include ketone peroxides (e.g., methyl ethyl ketone peroxide and cyclohexanone peroxide), peroxyketals (e.g., 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane and 2,2-bis(t-butylperoxybutane)), hydroperoxides (e.g., t-butyl hydroperoxide and 2,5-dimethylhexane-2,5-dihydroperoxide), dialkyl peroxides (e.g., dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexyne-3, and α,α′-bis(t-butylperoxy-m-isopropyl)benzene), diacyl peroxides (e.g., octanoyl peroxide and isobutyryl peroxide), and peroxycarbonates (e.g., peroxydicarbonates such as di(4-t-butylcyclohexyl)peroxydicarbonate).
[0061] The curing agent is not limited and is generally an agent useful for initiating the curing of the relevant polymer, oligomer, and / or monomer contained in the film composition. Examples include, but are not limited to, azides, peroxides, diazo compounds, sulfur, and sulfur derivatives. In a particularly preferred embodiment, the curing agent is peroxide-based. Suitable organic peroxides include dialkyl peroxide type (e.g., dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexyne-3, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, di-t-butyl peroxide, di-t-amyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, and 2,5-bis(t-butylperoxy)-2,5-dimethylhexane), peroxybenzoate type (e.g., t-butylperoxybenzoate ... Peroxides may include, but are not limited to, peroxyacyl types (e.g., t-butyl peroxyacetate), hydroperoxides (e.g., t-butyl hydroperoxide and 2,5-dimethylhexane-2,5-dihydroperoxide), diacyl peroxide types (e.g., lauroyl peroxide), dibenzoyl peroxide types (e.g., dibenzoyl peroxide and di-(4-methylbenzoyl) peroxide), ketone peroxide types (e.g., methyl ethyl ketone peroxide and cyclohexanone peroxide). Suitable carbon-carbon type initiators include, but are not limited to, 2,3-dimethyl-2,3-diphenylbutane and 3,4-dimethyl-3,4-diphenylhexane.
[0062] In a preferred embodiment, the rubber composition (B) also includes a peroxide-based radical initiator. In an embodiment, the free radical initiator source is selected with a decomposition 10-hour half-life temperature of at least 50°C. In an embodiment, the free radical initiator source is selected with a decomposition 10-hour half-life temperature of at least 100°C. The curing initiator, when used, is typically present in an amount of about 0.1% to about 5% by weight based on the total weight of the curable film. The loading and nature of the curing initiator can affect various properties, such as the lamination properties of the curable film and the post-lamination properties of the cured film, including, for example, the flow or rheology of the film, the time and temperature required to reach a proper or final cured state, and the post-lamination (or post-cure) properties, such as mechanical properties (e.g., modulus), expansion properties (e.g., CTE), and electrical properties (e.g., dissipation factor). Additionally, the shelf life (i.e., service life or useful life) of the curable film can be determined in part by the amount and selection of the initiator. In preferred embodiments, the curable films of the present invention have a long shelf life at room temperature of at least several weeks, months, or years, hi embodiments, the curable films have a shelf life at room temperature of at least one year.
[0063] <Liquid rubber> It may be beneficial to include one or more liquid diene-based rubbers (hereinafter sometimes referred to as liquid rubbers or "LR") in the rubber composition (B) of the curable film for the purpose of controlling the rheological profile upon application and heating, such as when the PCB layers are built on a platen press. For example, for the purpose of replacing prepregs in conventional PCB or HDI PCB manufacturing processes, the curable films of the present invention can be designed with suitable cure and flow properties to fill and flow copper traces and low pressure areas, allowing acceptable dielectric spacing in the final cured PCB assembly or subassembly. The inclusion of LR may also be used as a means to adjust the properties of the curable film in its cured or uncured state, for example, to adjust the Young's modulus, adhesion, electrical properties, or expansion properties.
[0064] While diene-based rubbers are elastomeric solids at ambient temperature, LR has a measurable viscosity at ambient or slightly elevated temperatures and is in the form of a liquid or resin. Because liquid rubbers do not have a sufficiently high molecular weight to behave as solid elastomers, LR can be considered as a lower molecular weight analogue of solid elastomers. Examples of liquid rubbers that can be used to realize the invention described herein are generally low molecular weight polymers and oligomers of their corresponding elastomeric rubbers described above. The molecular weight of LR can range from about 1,100 to about 11,000, about 1,300 to about 11,000, about 3,000 to about 11,000, or about 10,000 to about 55,000. For example, most industrially available styrene-butadiene copolymer (SBC) and polybutadiene (PBD)-based liquid rubbers have an average molecular weight of less than 10,000. Liquid ethylene-propylene-diene-monomer (EPDM) rubber and liquid ethylene-propylene rubber (EPR) typically have an average molecular weight of less than about 50,000. Other examples include liquid butadiene rubber (LBR), liquid isoprene rubber (LIR), liquid farnesene rubber (LFR), liquid farnesene-butadiene rubber (L-FBR), and liquid styrene-butadiene rubber (L-SBR), which may have a molecular weight ranging from about 1,300 to about 50,000.
[0065] The ideal content of solid diene rubber(s) and liquid rubber(s) in the rubber composition (B) of the curable film depends on various factors, including the viscosity of the liquid rubber, the stiffness of the elastomer, the total loading of filler, and consideration of whether the curable film or the cured body obtained from curing the curable film is designed to replace a core material of a PCB or a prepreg build-up material. When the rubber composition (B) of the curable film contains at least one LR having a high viscosity (e.g., >100,000 centipoise at 40°C), the LR is present at about 20% to about 60% by weight, preferably 40% to 60% by weight, and more preferably 50% to 60% by weight, based on the total weight of the curable film composition. When the rubber composition (B) contains at least one LR having a low viscosity (e.g., <100,000 centipoise at 40°C), the LR is present in a lesser amount of about 10% to about 40% by weight, preferably 10% to 30% by weight, and more preferably about 10% to 20% by weight, based on the total weight of the curable film composition. Type-5 curable films can be obtained with a ratio of diene rubber to liquid rubber ranging from about 1:5 to 1:0.1, and preferably from about 1:3 to 1:0.3. For example, if too much liquid rubber is incorporated in the composition, a Type-5 film cannot be obtained or the obtained curable film may have too high tackiness, so the specific combination of diene rubber(s) and liquid rubber(s) must be carefully specified for a given application of the curable film or the cured body obtained from curing the curable film, such as replacement of a coverlay prepreg or replacement of a core.
[0066] Preferably, the liquid rubber is co-curable with other components of the rubber composition (B). The LR can contain vinyl groups (i.e., 1,2 addition vs. 1,4 addition of dienes) and can have a high vinyl content (e.g., more than 70%, 80%, or 90% of suitable structural units having vinyl groups), a moderate vinyl content (e.g., between 30% and 70% of suitable structural units having vinyl groups), or a low vinyl content (e.g., less than 30% of suitable structural units having vinyl groups). The LR can be bio-derived or bio-based.
[0067] The liquid rubber can be modified or grafted LR containing elements other than hydrocarbons, such as maleic anhydride, maleic, carboxylated, hydroxylated, acrylated, siliconized, or epoxidized LR containing carboxy, hydroxy, acrylate, silicon, or epoxy functional groups. It should be noted that the inclusion of certain modified liquid diene rubbers can have a detrimental effect on the dielectric loss tangent of the cured film when incorporated in large amounts.
[0068] Commercially available liquid rubbers that can be incorporated into the rubber composition (B) include LRs manufactured by Cray Valley, Kuraray, Synthomer, and Evonik. Specific, but non-limiting examples of suitable primarily hydrocarbon only LRs include Ricon 300, Ricon 130, Ricon 131, Ricon 134, Ricon 154, Ricon 156, Ricon 157, Ricon 100, Ricon 184, Ricon 257, LIR-50, L-SBR-820, L-SBR-841, LIR290, Polyvest EP MV, Litheneactiv® 1000, and Lithene® ultra. Specific, but non-limiting, examples of modified LR include Ricon 130MA8, Ricon 130MA13, Ricon 130MA20, Ricon 603, Ricobond 1756, Ricobond 2031, Ricon CF MA8, Ricon MA6, Ricon 605 E, Polyvest EP MAT, Polyvest EP Mv, Poly BD 605E, Polyvest ST-E 60, Polyvest H, and LIR-410.
[0069] <Polyphenylene ether> Poly(arylene ethers) are commonly referred to in the art as polyphenylene ethers or poly(phenylene ethers), or simply "PPEs." The rubber composition (B) of the curable films described herein can include one or more PPEs, including modified or functionalized PPEs.
[0070] The incorporation of PPE can tailor the film properties, such as in limited cases where the film is highly tacky or difficult to release from the carrier. In addition to improving the handling properties of the uncured film, the introduction of PPE into the rubber composition (B) can also modify the properties (e.g., Tg, Young's modulus, and adhesive strength) of the resulting cured body. In particular, the inventors have surprisingly found that the incorporation of PPE or modified PPE material in an amount of about 5% to about 30% by weight, or more preferably about 7% to about 15% by weight, based on the total weight of the rubber composition (B) of the curable film, can significantly improve the release of the curable film from its carrier, reduce the tack of the curable film (e.g., in cases where LR is present in the rubber composition (B)), and even convert the formulation of a composition that would otherwise only be able to produce a Type-3 film into a composition that produces a Type-4 or Type-5 film. The mechanism is unknown, but without wishing to be bound by theory, the inventors believe that the PPE-based materials are rigid-rods and likely act as stiffeners to assist the elastomeric composition of the curable film, thus facilitating the release of the curable film from the carrier.
[0071] The type of PPE-based material contained in rubber composition (B) is not particularly limited, but it is preferable that the PPE-based material is co-curable with the diene elastomer or other components contained in rubber composition (B).
[0072] A poly(arylene ether) comprises a plurality of structural units of formula (1). [ka]
[0073] wherein each of R and R′ is independently hydrogen, halogen, primary or secondary C 1~7 Alkyl, Phenyl, C 1~7 Aminoalkyl, C 1~7 Alkenyl alkyl, C 1~7Alkynylalkyl, C 1~7 Alkoxy, C 6~10 Aryl and C 6~10 In some embodiments, each R is independently C 1~7 Alkyl or phenyl, for example, C 1~4 R' is alkyl and each R' is independently hydrogen or methyl. The PPE can be a homopolymer or a copolymer, including a graft or block copolymer. Combinations of the various forms can be used.
[0074] Exemplary poly(arylene ethers) include poly(2,6-dimethyl-1,4-phenylene ether), poly(2,6-diethyl-1,4-phenylene ether), poly(2,6-dipropyl-1,4-phenylene ether), poly(2-methyl-6-allyl-1,4-phenylene ether), poly(di-tert-butyldimethoxy-1,4-phenylene ether), poly(2,6-dichloromethyl ... Useful poly(arylene ethers) include poly(2,6-dibromomethyl-1,4-phenylene ether), poly(2,6-di(2-chloroethyl)-1,4-phenylene ether), poly(2,6-ditolyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), poly(2,6-diphenyl-1,4-phenylene ether), and poly(2,5-dimethyl-1,4-phenylene ether). Useful poly(arylene ethers) contain 2,6-dimethyl-1,4-phenylene ether units, optionally in combination with 2,3,6-trimethyl-1,4-phenylene ether units.
[0075] The PPE may be functionalized such that it has reactive groups that allow it to participate in the curing behavior of the curable film, for example by covalently incorporating into the rubber-based matrix. In a preferred embodiment, the PPE oligomer or polymer has reactive moieties or end groups that allow for improved properties of the rubber-based film. The PPE can be functionalized to provide functional groups that can improve adhesion between the conductive metal and dielectric layers used to form the wiring layer, and improve other processing and performance properties. For example, the PPE can be modified by using a functional compound that has either or both of (i) a carbon-carbon double bond or a carbon-carbon triple bond, and (ii) one or more carboxy groups, including carboxylic acids, anhydrides, amides, esters, and acid halides. In one embodiment, the functional group is a carboxylic acid or ester group. Examples of polyfunctional compounds that can provide carboxylic acid functional groups include maleic acid, maleic anhydride, fumaric acid, and citric acid.
[0076] In particular, suitable functionalized PPEs include the reaction product of poly(arylene ether) with a cyclic carboxylic acid anhydride. Examples of suitable cyclic anhydrides are maleic anhydride, succinic anhydride, glutaric anhydride, adipic anhydride, and phthalic anhydride, more preferably maleic anhydride or methacrylic anhydride. Maleated PPEs can be produced by the method described in U.S. Pat. No. 5,310,820 (Nelissen et al.) or are commercially available.
[0077] Commercially available examples of suitable modified poly(arylene ethers) include the acrylate-terminated difunctional poly(arylene) ethers SA90 and SA9000 manufactured by Sabic Corporation, and PPE-MA (maleated poly(arylene ether)) manufactured by Asahi Kasei Corp. Commercially available examples of suitable unmodified poly(arylene ethers) include Blendex HPP820 manufactured by Chemtura Corporation.
[0078] In an embodiment of the present invention, the curable film comprises at least one PPE, its oligomer, or PPE and its oligomer. The one or more PPEs preferably contain two or more unsaturated groups, such as triple bonds, vinyl, alkenyl, and acrylate-type groups, at both ends of the molecular chain. For example, a suitable functionalized poly(arylene ether) comprises the reaction of a poly(arylene ether) with a styrene-containing compound, such that after the reaction, there are unreacted double bonds in the resulting polymer. See formula (2). [ka]
[0079] In the formula, Y is selected from the group consisting of bisphenol A type, bisphenol F type, bisphenol S type, naphthalene type, anthracene type, biphenyl type, tetramethylbiphenyl type, phenol novolac type, cresol novolac type, bisphenol A novolac type, and bisphenol S novolac type groups, and m and n are each independently a natural number of 3 to 200.
[0080] [Filler] <Hollow Glass Microspheres (HGM)> The hollow glass microspheres (HGM) used in the curable film compositions of the present invention are typically borosilicate microspheres made from soda-lime borosilicate glass. HGM made from other types of glass may also be used. Borosilicate microspheres contain primarily SiO2 and at least 1% B2O3, although the glass composition of the microspheres can vary to some extent depending on the starting material. An exemplary soda-lime borosilicate contains 80.7% by weight SiO2, 6.9% by weight Na2O, 10.3% by weight CaO, 2.1% by weight B2O3, and 1.9% impurities.
[0081] Several methods are available for producing the HGM used in the present invention. A common approach involves the decomposition of a substance at very high temperatures to form a gaseous composition within the droplets. The rapid expansion of the gaseous composition at high temperatures causes the formation of bubbles. The hollow droplets are then rapidly cooled from the liquid state to form hollow microspheres. U.S. Pat. No. 3,699,050 (Henderson) discloses a dry gel process for making HGM. In this process, a solution of glass-forming oxides is dried to a hard residue or gel that is then crushed to the appropriate particle size. The crushed material is sieved to a narrow size range and then mechanically dropped through a high temperature furnace or spray tower. It appears that chemically bound water in the gel causes the particles to expand as the surface melts, forming hollow glass microspheres. Blowing agents can also be used to make HGM. U.S. Pat. No. 4,904,293 (Garnier et al.) discloses the production of microspheres having a high silica content, in which a starting glass is reduced to fine particles by grinding, optionally mixed with a blowing agent, and then passed through a burner flame at a temperature of over 1500° C. to form molten hollow microspheres which are subsequently cooled to form solid hollow microspheres.
[0082] Alternatively, HGM can be made by mixing borosilicate glass with traces of sulfur-containing compounds, such as sodium sulfate. The mixture is then dropped into a hot flame that melts the powdered glass and sodium sulfate. The melting of the sodium sulfate results in a decomposition reaction that releases traces of sulfur gas that form bubbles within the molten glass droplet. However, such HGM is usually not preferred for making circuit materials, since sulfur-containing compounds or other such polar compounds tend to have adverse effects during processing of the circuit materials. Instead, it is preferred that the gas composition inside the microspheres contains inert, non-polar, sulfur-free gases, such as nitrogen, carbon dioxide, and oxygen. The content of undesirable polar compounds, such as sulfur dioxide, should be controlled to less than 1% by weight.
[0083] At least 95% by weight of the gas composition contained in the HGM used in some embodiments of the present invention is inert, consisting primarily of nitrogen, followed by carbon dioxide, oxygen, and argon.
[0084] The hollow glass microspheres have a D50 of 30 μm or less. Preferably, the HGM has a D50 of less than 20 μm, more preferably 19.5 μm or 18 μm or less. Even more preferably, the HGM has a D50 of about 15 μm or less. Most preferably, the HGM has a D50 of about 12 μm or less, and a D95 of less than about 19.8 μm. In some embodiments, the HGM included in the curable film can have a D50 ranging from about 1 μm to about 30 μm (e.g., 2 μm, 4 μm, 6 μm, 9 μm, 11 μm, 15 μm, 18 μm, 20 μm, 26 μm, 28 μm, and 30 μm). In some embodiments, the HGM included in the curable film can have a D95 ranging from about 2 μm to 45 μm (e.g., 3 μm, 5 μm, 6 μm, 9 μm, 11 μm, 14 μm, 17 μm, 22 μm, 28 μm, 33 μm, 36 μm, and 39 μm). In some embodiments, the HGM included in the curable film can have a D99 ranging from about 1 μm to 45 μm (e.g., 2 μm, 5 μm, 6 μm, 9 μm, 11 μm, 15 μm, 19 μm, 24 μm, 28 μm, 30 μm, 36 μm, and 39 μm).
[0085] The particle size and particle size distribution of the HGM must be carefully selected and controlled, especially if it is desired to prepare "thin" films. For example, while both HGM having an average particle size of about 35 μm and HGM having an average particle size of about 12 μm can be used to make Type-5 films, the former has been found to be unsuitable for making thin films having thicknesses on the order of about 20 μm to 60 μm due to the insufficient peel strength (e.g., <2 pounds per inch (lb / in)) provided by the larger particle size.
[0086] The density of the hollow glass microspheres is 0.1 g / cc or more, preferably 0.2-0.6 g / cc, and more preferably 0.3-0.5 g / cc. In some embodiments, the HGMs can be used as supplied and without any special surface pretreatment, such as acid or alkali treatment. In some embodiments, the HGMs may be modified with surface functionalizing agents, such as silane coupling agents, to improve their compatibility with polymer matrices.
[0087] Commercially available hollow glass microspheres may be used, such as HGM manufactured by Trelleborg Offshore (Boston), Emerson and Cumming Corporation, W. R. Grace and Company (Canton, Massachusetts), and 3M Company (St. Paul, Minnesota), which are sold in a variety of grades with different densities, sizes, and coatings.
[0088] <Silica> The curable film of the present invention may contain silica. Although there is no particular limitation on the type of silica, fused silica is preferred. The fused silica may have an amorphous or spherical morphology. The fused silica may have a D50 of about 0.1 to 50 μm, or about 0.1 to 10 μm, or about 0.1 to 1 μm.
[0089] The curable film may contain silica in a volume content of about 10-70% by volume, or about 20-60% by volume, or about 40-55% by volume, or about 10-40% by volume, based on the curable film. The curable film may contain silica in a weight content of about 10-90% by weight, or about 20-70% by weight, or about 40-65% by weight, based on the curable film.
[0090] The silica may be surface modified and / or functionalized. For example, functionalized fused silica may be prepared by reacting a silane containing a functional group. The functional group may include at least one of (meth)acrylate, vinyl, allyl, propargyl, butenyl, styryl, aliphatic, and fluorinated groups.
[0091] Examples of (meth)acrylate functional silanes include (3-acryloxypropyl)trimethoxy-silane, n-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, (3-acryloxypropyl)methyldimethoxysilane, methacryloxypropyltrimethoxysilane, o-(methacryloxyethyl)-n-(triethoxy-silylpropyl)urethane, n-(3-methacryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxypropyltriethoxysilane, (methacryloxymethyl)methyldiethoxysilane, (methacryloxymethyl)methyldimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropylmethyldimethoxysilane, methacryloxypropyldimethylethoxysilane, and methacryloxypropyldimethylmethoxysilane. Examples of vinyl-functional silanes are vinyltriacetoxysilane, vinyltriethoxysilane, vinyltriisopropenoxysilane, vinyltriisopropoxysilane, vinyltrimethoxysilane, vinyltris(2-methoxyethoxy)silane, vinyltris(methylethylketoxyimino)silane, (divinylmethylsilylethyl)triethoxysilane, docosenyltriethoxysilane, hexadecafluorododec-11-enyl-1-trimethoxysilane, hexenyltriethoxysilane, 7-octenyltrimethoxysilane, silane, o-undecenyltrimethoxysilane, o-(vinyloxybutyl)-n-(triethoxysilyl-propyl)urethane, vinyltri-t-butoxysilane, vinyltris(methoxypropoxy)silane, vinylmethyldiethoxysilane, vinylmethyldimethoxysilane, vinyldimethylethoxysilane, trivinylmethoxysilane, bis(triethoxysilylethyl)vinylmethyl-silane, triethoxysilyl modified poly-1,2-butadiene, and diethoxymethylsilyl modified poly-1,2-butadiene.Examples of allyl-functional silanes include 3-(n-allylamino)propyltrimethoxysilane, n-allyl-aza-2,2-dimethoxysilacyclopentane, allyltrimethoxysilane, allyloxyundecyltrimethoxysilane, allyltriethoxysilane, and 2-(chloromethyl)allyltrimethoxysilane. An example of a propargyl-functional silane is o-(propargyloxy)-n-(triethoxy-silylpropyl)urethane. An example of a butenyl-functional silane is butenyltriethoxysilane. Examples of styryl-functional silanes include 3-(n-styrylmethyl-2-aminoethylamino)propyltrimethoxysilane and styrylethyltrimethoxysilane. An example of a cyclopentadienyl-functional silane is (3-cyclopentadienylpropyl)trimethoxysilane. Examples of cyclohexenyl-functional silanes include [2-(3-cyclohexenyl)ethyl]trimethoxysilane and [2-(3-cyclohexenyl)ethyl]trimethoxysilane. The functional silane may include at least one methacrylsilane selected from the group consisting of γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, and γ-methacryloxypropyltriethoxysilane.
[0092] <Other fillers> The curable film composition of the present invention may contain one or more fillers other than the hollow glass microspheres and / or silica to further adjust the dielectric constant, dielectric loss tangent, thermal expansion coefficient, thermal conductivity, and other properties of the cured product, preferably a particulate filler.
[0093] Examples of such particulate fillers include aluminum hydroxide, magnesium hydroxide, kaolin, talcum, hydrotalcite, calcium silicate, beryllium oxide, boron nitride, solid glass powder, fumed silica, silica powder, zinc borate, aluminum nitride, silicon nitride, silicon carbide, carborundum, corundum, alumina, magnesium oxide, zirconium oxide, mullite, titanium oxide, potassium titanate, barium titanate, strontium titanate, wollastonite, beryllia, alumina trihydrate, magnesia, mica, talc, nanoclay, and cenospheres, as described in U.S. Pat. No. 8,187,696 (Paul et al.). In some embodiments, the filler is surface treated with a silicon-containing coating. In some embodiments, a zirconate or titanate coupling agent is used to improve the dispersion of the filler in the polymer matrix and reduce water absorption.
[0094] The curable film may include a thermally conductive filler, examples of which include aluminum nitride, boron nitride, silicon carbide, diamond, nanodiamond, graphite, beryllium oxide, zinc oxide, zirconium silicate, magnesia, silica, or alumina.
[0095] [Maleimide resin] Maleimide resins are common additives to curable thermosetting compositions. The most widely used maleimides include bismaleimides (BMIs). BMIs are a type of maleimide-based resins that contain two maleimide groups in their molecular structure. They are known for their high reactivity towards amines and thiols, as well as their high thermal stability and good chemical resistance. They are widely used as comonomers or resin additives in structural composites where high thermomechanical stability is desired. Common BMIs that are commercially produced include, for example, 4,4'-diphenylmethane bismaleimides under the trade names BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-1100H, BMI-3000H, BMI-3000, BMI-4000, BMI-5100, BMI-7000H, BMI-7000, and BMI-TMI manufactured by DKK Corporation (Japan). Bismaleimide, m-phenylene bismaleimide, m-phenylene bismaleimide, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, and 1,6'-bismaleimide-(2,2,4-trimethyl)hexane.
[0096] Although there are thousands of known bismaleimides and hundreds of commercially available bismaleimides, only a very limited number of bismaleimides are suitable for incorporation into curable film compositions intended to be used as dielectric film materials after curing. In fact, a limited group of bismaleimides are commonly used as additives or base resins in curable film compositions intended to be used as dielectric layer, dielectric adhesive, and FCCL layer applications after curing. Suitable bismaleimides suitable for use as co-curable resins in uncured dielectric compositions are well known to those skilled in the art, as taught, for example, in U.S. Pat. No. 10,822,527 (Tochihira et al.). In general, BMIs in uncured dielectric compositions are used to improve the properties of the cured bodies made therewith. BMIs known to those skilled in the art to be useful for incorporation as resin additives or comonomers in curable film compositions for making dielectric electronic materials have the following properties:
[0097] (1) BMIs that increase the adhesion of the composition and the peel strength of the cured body: It is important that the BMI selected for use in the uncured composition used to make the cured body for dielectric applications be able to increase the adhesion of the composition during processing from the uncured to the cured body. This increased adhesion is important for reliable production of the cured body and also contributes to the peel strength of the cured body.
[0098] (2) BMIs that lower the CTE of the cured body: Those skilled in the art would be concerned that the thermomechanical stresses introduced by the dissimilar CTEs of the conductive layer (e.g., copper) and any insulating or dielectric layers would contribute to high failure rates during the thermal stresses required to fabricate devices that rely on combining dielectric and conductive layers. Thus, only BMIs with known thermal and dimensional stability within the ranges required to process the curable composition into a cured body are believed to be useful as resin additives or comonomers in uncured systems where thermal stresses may render the cured body inoperable or unreliable.
[0099] (3) BMIs that increase the decomposition temperature of the cured product: BMIs useful in uncured layers intended for end use as a cured product are required to withstand the thermal stresses of manufacturing, solder reflow, or other surface mounting processes in addition to the thermal stresses encountered during the life cycle of the cured product. Only BMIs that have sufficient thermal stability, meaning that they can maintain their electrical and mechanical properties even at high temperatures, are useful.
[0100] (4) BMI with high Tg and capable of increasing the Tg of the cured body: Those skilled in the art will be concerned that the cured body resulting from the uncured composition intended for use as a dielectric layer must have a sufficiently high Tg (i.e., >200°C). The requirement of high (Tg) is a fundamental teaching in the art of polymers suitable for dielectric material layers. Prior to the present invention, it was a core teaching in the art of polymer material science that a high Tg is important for dielectric materials used in, for example, PCBs, because it determines the thermal stability of the material. Tg is the temperature at which the material changes from a rigid glassy state to a soft rubbery state. In PCBs, for example, dielectric materials are exposed to elevated temperatures during the soldering and assembly process, as well as during normal use. If the Tg of the dielectric material is low, the material may soften and deform at these elevated temperatures, causing mechanical and electrical reliability problems. This may result in problems such as delamination, cracking, loss of insulation resistance, and catastrophic failure. Thus, in the current state of the art, and except for the teachings of the present invention, high Tg dielectric materials are believed to be necessary to ensure that the material maintains its mechanical and electrical properties at temperatures encountered in PCB manufacturing and use. A high Tg also allows for the use of more aggressive assembly processes such as reflow soldering without compromising the reliability of the board. One skilled in the art would thus only consider a BMI with a high Tg to be a suitable resin additive for incorporation into an uncured composition intended to be used to make a cured dielectric film, layer, or other cured body that is required to maintain thermomechanical and electrical properties.
[0101] (5) BMI to increase Young's modulus of the cured body: Young's modulus of a material is a measure of its stiffness or resistance to deformation under stress. It is a core belief and fundamental teaching in the chemistry of polymers used in dielectric layers that a high Young's modulus is desirable for a multi-layer dielectric cured body because it helps maintain the dimensional stability of the dielectric layer during manufacturing and use. For example, when a PCB is subjected to thermal and mechanical stresses during manufacturing and use, the dielectric material is subjected to compressive and tensile forces. A high Young's modulus helps ensure that the dielectric material does not deform excessively under these forces, which can result in mechanical reliability issues such as cracking, delamination, loss of insulation resistance, and catastrophic failure. In addition, a high Young's modulus helps ensure that the dielectric material retains its thickness and dimensional stability during thermal cycling, which can affect the overall performance of the cured dielectric body in the end-use application. This is especially important in HDI circuit boards where the dielectric thickness is tightly controlled to allow for small and closely spaced electrical traces. Thus, prior to the present invention, it was known that a high Young's modulus is required for dielectric layers, especially those used in PCBs, because it helps maintain the mechanical stability and reliability of the substrate and supports the use of high density, high performance designs. Thus, one skilled in the art would select only those BMIs that increase, or at least do not decrease, the Young's modulus of the cured body as resin additives or comonomers for incorporation into the uncured composition. This is especially true when the cured body is intended for use in PCBs, and even more so when the intended use of the cured body was a PCB using HDI design.
[0102] (6) BMI with limited solubility in common organic solvents: It is well known in the art that BMI suitable for use as a comonomer or resin additive in uncured thermosetting compositions intended to create a cured body should have limited solubility in common organic solvents such as acetone, toluene, methyl ethyl ketone, etc. It is also known that solubility in polar aprotic solvents such as N-methylpyrrolidone, dimethylacetamide, dimethylformamide, dimethylsulfoxide, etc. is acceptable. When using BMI as a comonomer or resin additive in uncured compositions intended to create a cured body for dielectric applications, low solubility in solvents is desirable because it ensures that the material retains its structural integrity and dimensional stability during processing and use. As is well known in the art, low solubility also makes it easier to control the thickness and uniformity of the dielectric layer, which is important to achieve the desired electrical properties and performance. In addition, low solubility can help reduce the risk of contamination of the dielectric layer during processing, which can negatively affect the electrical performance of the device. In contrast, if the BMI is highly soluble, control of layer thickness and uniformity may not be possible, and the material may dissolve or be contaminated during processing, which may result in reduced performance and reliability of electronic devices. High solubility in organic solvents, especially aromatic solvents, is undesirable. Particularly for uncured thermosetting compositions intended to create dielectric layers in electronic products, limited solubility in organic solvents is desirable because it helps ensure the stability and reliability of the composition before, during, and after curing due to minimal liberation of water resulting from ring-closing imidization during curing, as described, for example, in U.S. Pat. No. 4,924,005 (Darms). Organic solvents such as alcohols and ketones are commonly used in manufacturing processes involving thermosetting dielectric layers, such as cleaning, solvent-based etching, and surface treatment. If the BMI has high solubility in these solvents, it may dissolve and degrade, resulting in changes in the material properties of the uncured composition and the cured body resulting from the curing of the uncured composition.BMIs with high solubility in common organic solvents, when incorporated into uncured thermosetting compositions as comonomers or resin additives, can result in dimensional instability, inhomogeneous curing, poor adhesion, reduced peel strength, and degraded electrical performance, including undesirable changes in Dk and Df. This can negatively affect the stability, reliability, and performance of the uncured composition, the curing process, and the cured body resulting from the curing of the uncured composition. Undesirably high solubility can also make the curing process less predictable and less efficient. High solubility in organic solvents, including acetone, ethanol, polar organic solvents, or aromatic solvents, can also result in loss of adhesion between the cured body resulting from the uncured composition and other materials or layers in the end-use device, such as the substrate and metal traces of a PCB, which can result in delamination, mechanical unreliability, unpredictable thermomechanical properties, and degradation of electrical properties, including undesirable Dk and Df. Thus, it is generally taught that only BMIs of limited solubility are suitable for use as comonomers or resin additives in uncured thermosetting compositions to prevent dissolution, degradation, and loss of adhesion, and to maintain dimensional stability, electrical performance, and mechanical reliability of the cured body.
[0103] In summary, a person skilled in the art following the teachings of the existing technology would select only those BMIs for incorporation as comonomers or resin additives into uncured thermosetting compositions intended to produce dielectric layers after curing that have the following properties: (1) the ability to increase adhesion and peel strength of the cured product; (2) the ability to decrease the CTE of the cured product; (3) the ability to increase the decomposition temperature of the cured product; (4) the ability to increase the Tg of the cured product; (5) the ability to increase the Young's modulus of the cured product; and (6) acceptable high solubility in polar aprotic solvents such as N-methylpyrrolidone, dimethylacetamide, dimethylformamide, dimethylsulfoxide, etc., but low solubility in common organic solvents such as acetone, toluene, methyl ethyl ketone, etc. Thus, when selecting a comonomer or resin additive suitable for use in a curable composition the cured product of which is intended to be used as a dielectric film, one of ordinary skill in the art would be diligent in avoiding the selection of any BMI whose cured product would have a Tg less than 180°C, a Young's modulus less than 0.5 GPa, a CTE greater than 70 ppm / °C, and high solubility in common organic solvents, e.g., solubility in toluene greater than 15 g / 100 ml.
[0104] However, contrary to the knowledge of those skilled in the art, and in stark contrast to the teachings of, for example, U.S. Pat. No. 10,822,527 (Tochihira et al.), it has been found that commonly used BMIs that are believed to be suitable for use in curable films to create dielectric layers could not be incorporated into the curable film compositions of the present invention. The inventors have found that the incorporation of commonly used BMIs results in compositions that cannot be cured into films without the introduction of voids, holes, defects, crystalline precipitates, phase separation, or other defects that make the curable film non-uniform. For example, curable films prepared using compositions containing diene rubber / liquid rubber and only 1 wt.% BMI 5100 resulted in phase separation or crystallization of the BMI within the film.
[0105] It has surprisingly been found that BMI resins that are substantially soluble in toluene at concentrations of, for example, at least 10 g / 100 ml, at least 15 g / 100 ml, or even at least 20 g / 100 mL, can be incorporated as resin additives or comonomers into the curable film compositions of the present invention that result in cured films that are free of voids, defects, imperfections, phase separation, or thickness irregularities.
[0106] Preferred maleimide resins incorporated into the curable film compositions of the present invention are amorphous and have a solubility in toluene of at least 5 g / 100 ml, preferably at least 10 g / 100 ml, and more preferably at least 15 g / 100 ml at ambient temperature. Curable films containing such maleimide resins exhibit desirable high peel strengths (e.g., >6 lb / in) on LP (low roughness), VLP (very low roughness), or HVLP (very low roughness) copper foils, extremely low dissipation factor (Df) (e.g., <0.002, <0.0015, <0.0012, or even about 0.001), and low dielectric constants (Dk) ranging from about 1.9 to about 3.1. In certain embodiments, the maleimide resins used in the curable films of the present invention have good miscibility with diene rubbers, allowing for the creation of curable films with excellent properties (e.g., Type-5 films). For purposes of simplicity, the maleimide resins used in the curable film compositions of the present invention are referred to as "Greasy MR" or "GMR". It has been discovered that the combination of diene based rubber(s) and GMR(s) is useful for making suitable dielectric layers with low Tg and low modulus for a variety of applications, including for thermosetting PCB base materials, which is contrary to the teachings of the prior art as discussed above and throughout this application.
[0107] In an embodiment, the GMR is co-curable with a diene rubber. In an embodiment, the GMR that is co-curable with a diene rubber has a solubility in toluene of greater than 10 g / 100 ml at ambient temperature. In an embodiment, two or more GMRs are used.
[0108] The ratio of diene rubber(s) to GMR(s) is not particularly limited since it has been found that these components typically have excellent compatibility with each other. However, the ratio of diene rubber to GMR is preferably in the range of 1:0.1 to 1:2, and more preferably in the range of 1:0.2 to 1:0.8. In an embodiment, the ratio of diene rubber to GMR ranges from about 1:2 to about 1:1. In an embodiment, the ratio of diene rubber to GMR is greater than about 1:1, or greater than about 1:0.9, or greater than about 1:0.8, or greater than about 1:0.7, or greater than about 1:0.6. In another embodiment, the ratio of diene rubber to GMR is greater than about 1:0.5, or greater than about 1:0.4, or greater than about 1:0.3, or greater than about 1:0.2.
[0109] Suitable maleimide resins for the present invention contain unsaturation points that allow for free radical curing or other curing methods and may be molecular, monomeric, oligomeric, polymeric, or partially crosslinked in nature. Preferably, such maleimide resins contain two or more maleimide groups. It has been discovered that curable films that also include GMR have improved adhesive, physical, thermal, and / or electrical properties.
[0110] In embodiments, the GMR has a solubility in toluene of at least 5 g / 100 ml at ambient temperature. In embodiments, the GMR has a solubility in toluene of at least 10 g / 100 ml, e.g., greater than 20 g / 100 ml, or greater than 30 g / 100 ml, or greater than 40 g / 100 ml. In embodiments, the GMR has a solubility in toluene of greater than 40 wt / wt%, 50 wt / wt%, 60 wt / wt%, 70 wt / wt%, or 80 wt / wt% at ambient temperature.
[0111] In embodiments, GMR has a molecular weight greater than about 600. In embodiments, GMR has a molecular weight greater than about 1,000. In embodiments, GMR has a molecular weight less than about 100,000. In embodiments, GMR has a molecular weight greater than about 1,000 and a solubility in toluene of at least 10 g / 100 ml at ambient temperature. In embodiments, GMR has a molecular weight greater than about 1,000 and a solubility in toluene of at least 20 g / 100 ml at ambient temperature.
[0112] Suitable GMRs may have structures represented by the following formulas (3)-(5): [ka] [ka] [ka]
[0113] where n represents an integer from 1 to 100, and A, B, and C each represent a linking group that allows for a solubility in toluene at ambient temperature of at least 5 g / 100 ml or 10 g / 100 ml. A specific, but non-limiting example of formula 3 is GMI 2300 manufactured by SHIN-A T&C Co., Ltd. (Korea).
[0114] As far as the curable film is concerned, the exact molecular identity of the linking groups A, B, and C in formulas (3)-(5) is not particularly critical. The presence of an aliphatic chain (e.g., containing 10-50 carbon atoms) typically provides adequate solubility and helps ensure sufficient miscibility with diene-based rubbers. It is preferred that the linking group does not contain a large number of polar groups, as polar groups can worsen miscibility and / or increase the dielectric loss tangent of the cured film.
[0115] Specific, but non-limiting, examples of such suitable GMRs are GMIs derived from dimer or trimer fatty acids, and C 36 Included among these are GMIs derived from dimer or trimer fatty amines such as amines. Specific, but non-limiting, GMRs derived from dimer fatty acids can be represented by the following formulas (6)-(8): [ka] In the formula, n=1 to 100, [ka] In the formula, n=1 to 100, and [ka] In the formula, n=1 to 100.
[0116] The further incorporation of other BMIs into the curable film composition is possible so long as such incorporation does not serve to defeat the spirit of the present invention.
[0117] [Other additives] <Flame retardants> In order to have fire resistance or flame resistance, the curable film of the present invention or its cured product preferably also contains one or more flame retardants. In an embodiment, the curable film or its cured product may have a UL-94 rating of V0, V1, VTM-0, or VTM-1. The flame retardant may be added to the curable film in an amount of about 5 to 30% by weight based on the total weight of the curable film. For particulate flame retardants, particles having a D50 below 20 μm are preferred, more preferably below 10 μm, and even more preferably below 5 μm. The flame retardant may be surface-modified to enhance compatibility with other components of the curable film.
[0118] Flame retardants can be halogen-based or non-halogen-based, and non-halogen-based flame retardants are preferred due to environmental and health considerations. Non-halogen-based flame retardants can be phosphorus-based or inorganic. Examples of phosphorus-based flame retardants include melamine polyphosphate, aluminum diethylphosphonate, DOPO, and DOPO derivatives including DOPO-modified resins, triarylphosphonates (e.g., triphenyl phosphate (TPP)), dimeric aryl phosphates (e.g., resorcinol bis(diaryl phosphate), bisphenol A bis(diaryl phosphate)), and phosphonate oligomers, homopolymers, and copolymers. Commercially available phosphorus-based flame retardants include Exolit® OP935 or Exolit® OP945, which are aluminum polyphosphates available from Clariant, SPB100 or phosphazene available from Otsuka Chemical Co., Ltd., Altexia from Albemarle, PQ60 from Chin Yee Chemicals, and Nofia® OL series, CO series, and HM series products available from FRX Polymers (Chelmsford, Massachusetts, USA). Examples of inorganic flame retardants include ATH (aluminum trihydroxide) and MDH (magnesium hydroxide). Inorganic flame retardants are usually coated with organic materials to improve their compatibility with the polymer matrix. Halogen-based flame retardants such as Albemarle's Saytex 8010, ethylene-1,2-bis(pentabromophenyl), or BT93 can also be used.
[0119] <Adjuvants> The curable film may contain adjuvants that can be used to adjust the properties of the cured or uncured film. Such agents include antioxidants to promote the stability of the curable film or its cured form in field use, adhesion promoters to improve adhesion to the copper foil, compatibilizers to improve the interaction between the filler and the rubber composition (B), and rheology modifiers to improve the flow properties of the curable film during heat pressing. Some adjuvants can serve more than one purpose, for example, reactive monomers or crosslinkers can be used both to change the rheological profile of the curable film and to change the physical properties of the cured film in its cured form, for example, by increasing the modulus and decreasing the CTE.
[0120] The curable film may comprise hydrocarbyl thermoplastic polymers or other polymers such as styrene maleic anhydride. In an embodiment, the curable film comprises an alpha-olefin and a C 4~30 The hydrocarbyl thermoplastic polymer may include repeat units derived from a cycloalkene, a reactive monomer capable of free radically crosslinking to produce a crosslinked network, a free radical source, and a functionalized fused silica capable of chemically bonding to the crosslinked network. The hydrocarbyl thermoplastic polymer may include repeat units derived from at least one of cyclobutene, cyclopentene, cycloheptene, cyclooctene, cyclodecene, norbornene, and alkyl or aryl substituted norbornene (e.g., 5-methyl-2-norbornene, 5-hexyl-2-norbornene, 5-phenyl-2-norbornene, 5-ethyl-2-norbornene, 4,5-dimethyl-2-norbornene, exo-1,4,4a,9,9a,10-hexahydro-9,10(1',2')-benzeno-1,4-methanoanthracene, exo-dihydrodicyclopentadiene, and endo,exo-tetracyclododecene). The C to alpha-olefin repeat units may include at least one of cyclobutene, cyclopentene, cycloheptene, cyclooctene, norbornene ... 4-30The molar ratio of cycloalkene repeat units can be from 6:1 to 0.5:1, or from 6:1 to 1.5:1.0. The average molecular weight of the hydrocarbyl thermoplastic polymer can be from 500 to 105,000.
[0121] In one embodiment, co-curable coagents having a molecular weight greater than 500 are useful as additives to the curable film compositions of the present invention, provided that they are soluble in toluene at a level of at least 10 g of agent per 100 ml of toluene at ambient temperature. Examples of such coagents include co-curable polyphenylene ethers such as SA9000, co-curable vinyl modified maleimides as described in U.S. Pat. No. 11,066,520 (She), and co-curable poly(styrene-co-glycidyl methacrylate).
[0122] The curable film may include reactive monomers or reactive crosslinkers containing one or more unsaturated groups (e.g., vinylic, alkene, acetylenic, acrylate, cyanate ester, modified maleimide, and methacrylate). The use of reactive monomers or crosslinkers may serve the purpose of a rheology modifier for the curable film while modifying the modulus, thermal expansion properties, and / or electrical properties of the cured form of the curable film. The reactive monomer may include triallyl (iso)cyanurate. The reactive monomer may be exclusively from carbon and hydrogen. The reactive monomer may be styrenic. The reactive monomer may include a crosslinkable elastomer and may be a hydrocarbon resin diluent.
[0123] Crosslinkable elastomers include olefins (e.g., C olefins such as ethene, propene, butene, butadiene, piperylene, and isoprene). 2~8The crosslinkable elastomer may be derived from at least one of cyclic olefins (e.g., norbornene-type monomers containing unsaturated side groups, such as 5-vinyl-2-norbornene) and alkenes). However, the crosslinkable elastomer contains at least one of unsaturation in the backbone and unsaturated side groups. Examples of crosslinkable elastomers are elastomers derived from ethene, propene, and dicyclopentadiene. When the curable film contains a crosslinkable elastomer containing repeat units derived from a cyclic olefin, it can be distinguished from a hydrocarbyl thermoplastic polymer in the following respects. That is, the hydrocarbyl thermoplastic polymer may not contain a crosslinkable group, or the crosslinkable elastomer may have a lower weight average molecular weight. For example, the crosslinkable elastomer may have a weight average molecular weight of 500 to 50,000, or 500 to 10,000, or 200 to 2,500, and the hydrocarbyl thermoplastic polymer may have a weight average molecular weight of 70,000 to 105,000. An example of a crosslinkable ethene-propene-dicyclopentadiene elastomer is TRILENE® 65D, available from Lion Elastomers, Geismar, Louisiana.
[0124] The curable film may include a hydrocarbon resin diluent. The curable film may include 0-50 volume %, or 5-40 volume %, or 10-30 volume % of the hydrocarbon resin diluent, based on the total volume of the curable film. The addition of the hydrocarbon resin diluent may result in at least one of reduced minimum melt viscosity, enhanced resin flow, and improved leveling.
[0125] The hydrocarbon resin diluent can be saturated. The hydrocarbon resin diluent can include amorphous thermoplastic oligomers or polymers produced by polymerization of unsaturated hydrocarbons. As used herein, the hydrocarbon resin diluent oligomer can have a weight average molecular weight of 2,500 or less.
[0126] Hydrocarbon resin diluents are C 2~9 The hydrocarbon resin diluent may include an aliphatic C2~9 Hydrocarbon or aromatic C 6~9 The hydrocarbon resin diluent may be derived from at least one of the following hydrocarbons: 5~25 The hydrocarbon resin diluent may be free of repeat units derived from a cycloalkene. The hydrocarbon resin diluent may include repeat units derived from a cyclooctene.
[0127] The hydrocarbon resin diluent may include polybutene or oligomeric polybutene. Oligomers of C4 olefins, primarily isobutene, are commercially available in a wide range of weight average molecular weights. Short chain length polybutenes are flowable, medium chain length polybutenes are sticky with a honey-like consistency, while the longest chain lengths are tacky semi-solids. Examples of polybutenes include INDOPOL®, available from Ineos Oligomers, London, and PANALANE®, available from Vantage Specialty Ingredients, Warren, New Jersey.
[0128] The hydrocarbon resin diluent may be derived from piperylene and optionally aromatic repeat units. The hydrocarbon resin diluent may include a C5 hydrocarbon resin diluent that may be prepared from piperylene, or its derivatives, such as at least one of cis / trans 1,3-pentadiene, 2-methyl-2-butene, cyclopentene, cyclopentadiene (CPD), and dicyclopentadiene (DCPD). Piperylene monomers and their derivatives may be cationic polymerized using Lewis acid catalysts to produce oligomeric resins with low to high softening points. The C5 hydrocarbon resin diluent may be primarily aliphatic and therefore compatible with at least one of natural rubber, styrene-isoprene-styrene (SIS) copolymers, amorphous polyolefins (APOs) (e.g., amorphous polyalpha-olefins (APAOs)), polyolefins (e.g., low density polyethylenes (LDPEs)), synthetic elastomers, and low polarity cyclic olefin copolymers (COCs). The C5 hydrocarbon resin diluent may have a weight average molecular weight of 200 to 2,500. The C5 hydrocarbon resin diluent may have a softening point of 85 to 115°C (solid grades) or 5 to 10°C (liquid grades). The C5 hydrocarbon resin diluent may be hydrogenated to reduce discoloration and improve thermo-oxidative and UV stability. Examples of C5 hydrocarbon resin diluents include WINGTACK® 10, WINGTACK® 95, and WINGTACK® 98, available from Cray Valley, Exton, Pennsylvania.
[0129] Hydrocarbon resin diluents are C 8~9 The hydrocarbon resin diluent may, for example, contain aromatic repeating units. 8~9 Hydrocarbon resin diluents can be prepared from coal tar or crude oil distillates, such as indene, methylindene, styrene, methylstyrene (e.g., alpha-methylstyrene), and vinyltoluene. 8~9 Hydrocarbon monomers can be cationic polymerized using Lewis acid catalysts to produce oligomeric resins ranging in weight average molecular weight. Compared to C5 hydrocarbon resin diluents, aromatic C8~9 Hydrocarbon resin diluents can have higher melt viscosities and softening points (100-150°C). 8~9 The hydrocarbon resin diluents are also compatible with a variety of polymers.
[0130] Hydrocarbon resin diluents include C5 resin diluents and C 8~9 Both the C5 and C6 hydrocarbon resin diluents may be included, for example as blends or co-oligomers or copolymers thereof. 8~9 Curable films of hydrocarbon resin diluents (e.g., as blends or copolymers) may contain 0 to 50 weight percent, or 1 to 50 weight percent, or 5 to 25 weight percent aromatic repeat units, based on the total weight of the diluent. 8~9 Examples of modified C5 hydrocarbon resin diluents are Wingtack® STS, Wingtack® Extra, and Wingtack® 86 available from Cray Valley.
[0131] The hydrocarbon resin diluent may include any blend or cooligomer or copolymer of the disclosed hydrocarbon resin diluents. For example, the hydrocarbon resin diluent may include aliphatic C5, aromatic C9, cooligomer or copolymer derived from petroleum-based feedstocks such as styrene, ethylene, propylene, and butadiene. The hydrocarbon resin diluent may include at least one of styrene-ethylene butadiene-styrene copolymers or styrene-propylene butadiene-styrene copolymers, which may be optionally hydrogenated. An example of such a hydrocarbon resin diluent is REGALREZ® resin, available from Eastman Company.
[0132] Hydrocarbon resin diluents can be distinguished from hydrocarbyl thermoplastic polymers in that at least one of the following is true: 1) the diluent can have a lower weight average molecular weight, e.g., the weight average molecular weight of the diluent can be 60% or less of the weight average molecular weight of the hydrocarbyl thermoplastic polymer, 2) the diluent can have a lower heat distortion temperature point, 3) the diluent can have a lower glass transition temperature, and 4) the diluent can be reactive. One or more of these distinguishing features can enable the hydrocarbon resin diluent to have a plasticizing effect on the hydrocarbyl thermoplastic polymer and ceramic filled versions thereof, thereby improving the flow of the resin and reducing the minimum melt viscosity of the formulation system.
[0133] The hydrocarbon resin diluent may have a weight average molecular weight of 200 to 2,500, or 1,000 to 2,200, or 1,000 to 8,000. The hydrocarbon resin diluent may have a number average molecular weight of 150 to 6,000, or 200 to 2,200.
[0134] Other adjuvants that can be included in the curable films include colorants (e.g., dyes and pigments), plasticizers, cure retarders, cure accelerators, impact modifiers, UV inhibitors, heat stabilizers, light stabilizers, radical stabilizers, antistatic agents, preservatives, toughening agents, rubber particles, lubricants, mold release agents, foaming agents, biocides, processing aids, acid scavengers, nucleating agents, nanotubes, wetting agents, dispersants, synergists, reinforcing agents, whiskers, and smoke suppressants.
[0135] [Method for producing a curable film] The method for preparing the curable film of the present invention is described below. In some embodiments, the curable film is provided on a substrate. Suitable substrates can be plastic films, metal foils, papers, woven fabrics, nonwoven fabrics, etc., with one or both sides optionally subjected to a release treatment.
[0136] The methods of making the curable film described herein include solvent casting, melt extrusion, lamination, and coating.Non-limiting examples of solvent casting, melt extrusion, lamination, and coating can be found, for example, in US Patent Application Publication No. 2005 / 0133953, US Patent Application Publication No. 2009 / 0050842, US Patent Application Publication No. 2009 / 0054638, US Patent Application Publication No. 2009 / 0096962, and US Patent Application Publication No. 2010 / 0055356, the contents of which are incorporated herein by reference.Further examples of solvent casting, melt extrusion, lamination, and coating methods for forming films can be found, for example, in US Patent No. 4,592,885 and US Patent No. 7,172,713, the contents of which are also incorporated herein by reference.
[0137] Although in some embodiments it may be possible to produce curable films by solventless processes (e.g., melt extrusion), continuous solvent casting processes (e.g., coating processes) are preferred methods for preparing the curable dielectric films described herein because solvent casting processes can provide films having high quality and uniform thickness.
[0138] The curable film of the present invention can be prepared by coating the varnish composition on a substrate, such as a carrier film and copper foil, followed by drying to remove the volatile solvent. The varnish composition, which is a dispersion of the components of the curable film composition in a solvent, is essentially a precursor to the curable film. Suitable solvents include, but are not limited to, toluene, 1,3 dioxalane, ethyl acetate, and any mixtures thereof. In some embodiments, the varnish composition is stable for several days (i.e., until the varnish gels due to the curing of certain composition components). In some embodiments, the varnish composition is stable for weeks, months, or years before gelation occurs.
[0139] Examples of methods for coating include conventional coating methods and printing methods. Specific examples of coating methods can include air doctor coating, bar coating, blade coating, knife coating, reverse coating, transfer roll coating, gravure roll coating, kiss coating, cast coating, spray coating, slot die coating, calendar coating, dam coating, dip coating, and die coating. Specific examples of printing methods can include intaglio printing, such as gravure printing, and stencil printing, such as screen printing.
[0140] The drying conditions for removing the solvent are not particularly limited, but it is preferable that the drying is carried out at a temperature within the range of 60 to 150 ° C, appropriately adjusted depending on the solvent used in the varnish composition. Drying temperatures lower than 60 ° C are usually not preferred because the solvent is likely to remain in the film. In addition, low drying temperatures coupled with the evaporation of the solvent can cause condensation and phase separation or precipitation of the resin components. Drying at elevated temperatures for a long period of time, especially at temperatures higher than 150 ° C, is also not preferred because premature curing of the film can occur.
[0141] A typical solvent casting process includes the steps of (1) dissolving and / or dispersing ingredients (e.g., rubbers, fillers, initiators, and other ingredients, such as flame retardants, other organic polymers, oligomers, and molecules) in a solvent to make a varnish, (2) coating the varnish on a substrate, and (3) evaporating / removing the solvent by drying (e.g., drying in an oven) to result in a film on the substrate. The final thickness of the film can be controlled, for example, by passing the varnish through a slot die. Typically, for the casting process to result in a high quality film, it is important that the polymer and other organic-based ingredients are dissolved in the varnish solvent and that the filler ingredients are well dispersed. The residence time and temperature profile of the oven will dictate factors such as the amount of residual solvent retained in the film and whether the film is partially cured or cured into a crosslinked polymer composition, or whether the composition remains a blend (e.g., still has thermoplastic qualities). In some embodiments, the composition is a thermoplastic polymer composition after the film casting and drying process. In some embodiments, the composition is a thermosetting polymer composition after the film casting and drying process. In some other embodiments, the polymer composition is a crosslinked thermoplastic composition after the film casting and drying process.
[0142] In some embodiments, the curable film is manufactured or provided on a substrate such as a metal (e.g., copper, aluminum) foil, a disposable plastic carrier or release film, or other common carrier or release liner. Non-limiting examples of preferred plastic carriers or release films include polyethylene film, polypropylene film, polymethylpentene film, polyethylene terephthalate (PET) film, fluoropolymer film, polyethylene coated paper, polypropylene coated paper, and silicone releasable paper. The carrier or release film may be treated with a release coating on one or both sides. For a release substrate utilizing a plastic film as a base material, the thickness of the plastic film is preferably about 10-100 μm, while for a release substrate utilizing paper as a base material, the thickness of the release paper is preferably about 50-200 μm. In some embodiments, the curable film manufactured on such a carrier or release film may be further laminated. In some embodiments, the curable film produced on such a carrier or release film can be further laminated with another release film or paper, for example as a protective layer, such that both sides of the curable film are in contact with the releasable carrier film, which can later be removed to expose the curable film and be used.
[0143] In some embodiments, the curable film is coated directly onto a metal foil, such as copper or aluminum foil. Preferably, the copper foil is about 3-35 μm thick. The roughness of the copper foil can be standard HTE (High-Tensile Elongation) "shiny", LP (low roughness), VLP (very low roughness), HVLP (very low roughness), or ANP (almost no roughness). The metal foil may be treated with an adhesion promoter, such as a silane coupling agent. In some embodiments, the curable film is coated directly onto the copper foil, and then a protective carrier or release film is laminated thereon. In some embodiments, the curable film can be coated with sputtered copper, for example by physical vapor deposition, to a thickness of 0.5-5.0 μm. In some embodiments, the laminate is made by laminating copper foils coated with the curable film of the present invention and then pressing them together by hot roll lamination or by pressing using a batch process with a platen press.
[0144] In some embodiments, the curable film is tack-free to the touch. In some embodiments, the curable film is a type-4 or type-5 film that has sufficient plasticity so that it can be peeled off from the carrier film and placed on an object, which can be a copper foil or sheet, a copper clad (etched, partially etched, or unetched), or a copper unclad fiberglass core. In some embodiments, an assembly is formed in which the curable film (e.g., a type-3 film) on the carrier film is placed on a substrate with its free surface side (i.e., the side opposite the side of the curable film that contacts the carrier film), the assembly is passed through a roll laminator, and then the carrier film is peeled off, leaving the curable film on a new substrate, which can be a copper foil or sheet, a copper clad (etched, partially etched, or unetched), or a copper unclad fiberglass core. In some embodiments, the curable film is metal (e.g., copper) clad or unclad. In some embodiments, the curable film is unreinforced (e.g., does not include woven or nonwoven glass fabric or organic fabric).
[0145] [Characteristics of the curable film and the cured product obtained by curing the curable film] Here, the "cured body obtained from curing the curable film" can be a cured film obtained by curing the curable film of the present invention, or any product containing the curable film after partial or complete curing. In some embodiments, the curable film and the cured body obtained from curing the curable film are substantially isotropic. In some embodiments, all of the components of component (B) in the curable film or the cured film obtained therefrom are substantially miscible. The thickness of the curable film or the cured film obtained therefrom typically ranges from about 0.2 mils to about 16 mils (i.e., about 5 μm to about 400 μm), preferably from about 0.4 mils to about 10 mils (i.e., about 10 μm to about 250 μm), and more preferably from about 0.5 mils to 4 mils (i.e., about 12 μm to about 100 μm). In some embodiments, the thickness is approximately 10 μm, 12.5 μm, 15 μm, 20 μm, 25 μm, 30 μm, 40 μm, or 45 μm. In some embodiments, the thickness is approximately 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, or 105 μm. In some embodiments, the thickness is about 100 μm to about 200 μm. In some embodiments, the curable films can be stacked to achieve a thickness of about 2 mils to about 10 mils, or about 11 mils to about 60 mils.
[0146] The curable film may have a minimum melt viscosity of about 1,000 Pa·s to about 1,000,000 Pa·s as determined by rheometry at 0.1% strain. In some embodiments, the curable film may have a minimum melt viscosity of about 1,000 Pa·s to about 100,000 Pa·s as determined by rheometry at 0.1% strain. In some embodiments, the curable film may have a minimum melt viscosity of about 2,000 Pa·s to about 10,000 Pa·s as determined by rheometry at 0.1% strain. In some embodiments, the curable film may have a minimum melt viscosity of about 5,000 Pa·s to about 20,000 Pa·s as determined by rheometry at 0.1% strain. In some embodiments, the curable film may have a minimum melt viscosity of about 20,000 Pa·s to about 80,000 Pa·s as determined by rheometry at 0.1% strain. In some embodiments, the curable film may have a minimum melt viscosity of about 80,000 Pa·s to about 200,000 Pa·s as determined by rheometry at 0.1% strain. In some embodiments, the curable film may have a minimum melt viscosity of about 200,000 Pa·s to about 1,000,000 Pa·s as determined by rheometry at 0.1% strain. In some embodiments, the minimum melt viscosity occurs at about 80° C. to about 200° C., or about 80° C. to about 160° C., or about 100° C. to about 150° C. as determined by rheometry at 0.1% strain.
[0147] In some embodiments, the curable film is a Type-3 film, in some embodiments, the curable film is a Type-4 film, and in some other embodiments, the curable film is a Type-5 film. In some embodiments, the curable film formed on the carrier film can be laminated or heat pressed with the carrier film attached, and the carrier film is then removed to expose the curable film or the resulting cured film that is placed on a new substrate. In some embodiments, the free surface of the curable film, which is the surface opposite to the surface that contacts the carrier film, can be contacted with a new substrate, and the thus formed assembly of the new substrate and the curable film on the carrier film can be passed through a roll laminator, and the curable film can then be transferred from the carrier film to the new substrate. In some embodiments, the curable film can be removed from the carrier or release film and placed on a substrate. In some embodiments, the curable film is tack-free to the touch. In some embodiments, the curable film has sufficient plasticity such that it is a Type-5 film and can be manipulated and placed on another object after being peeled from the carrier film.
[0148] The curable films of the present invention have a remarkable long shelf life. Currently available curable dielectric films tend to have a limited shelf life due to factors such as moisture absorption, chemical degradation, and aging. Many curable dielectric materials have a high affinity for water and can absorb moisture from the air over time. This can lead to changes in the electrical properties of the material, such as a decrease in insulation resistance and an increase in dielectric constant. Moisture in the curable film can also cause blisters during lamination with copper, and can cause the curable film material to swell or delaminate from the substrate, which can lead to electrical failure. Curable films for making dielectric materials can also be chemically degraded by exposure to light, heat, or other environmental factors. Curable films are highly susceptible to chemical degradation over time, especially when stored at or above refrigeration temperatures. Chemical degradation can result in changes in the electrical properties of the material, such as changes in dielectric strength and increases in dielectric loss, and can cause the dielectric material to become brittle, which can lead to cracking and significant degradation of electrical and thermomechanical properties over time. In addition, dielectric films can undergo aging, which is a time- and temperature-dependent change in the properties of a material. Aging can occur due to exposure to environmental factors such as heat and radiation or due to the inherent properties of the material. As dielectric material films age, their electrical properties can change, which can lead to reduced performance and eventual failure. In the case of curable films for making dielectric layers, aging can harden the uncured film over time, which can change the rheological, electrical, and thermomechanical properties of the curable film.
[0149] For these reasons, commercially available curable films and curable prepregs require refrigerated storage at temperatures below 5° C. to allow a shelf life of up to 180 days. In addition, commercially available curable films typically require humidity-controlled refrigerated storage in metallized bags to allow a shelf life of at least 90 days or 3 months. In contrast, the curable films of the present invention can achieve a shelf life of more than 90 days at ambient temperature without humidity control. Some embodiments have a shelf life of at least 6 months, at least 12 months, or at least 18 months, even when stored at ambient temperature, in or without a metallized bag, with or without controlled humidity conditions.
[0150] The cured body resulting from curing the curable film of the present invention may have a peel strength of at least 2.2 lb / in on multiple grades of copper foil including standard HTE (high elongation) "shiny" copper with a feature size of >7 micrometers, LP (low roughness) copper foil with a feature size of 5.1-9.9 micrometers, VLP (very low roughness) copper foil with a feature size of >2 micrometers and <5 micrometers, HVLP (very low roughness) copper foil with a feature size of >0.5 micrometers and <2 micrometers, and ANP (almost no roughness) copper foil with a feature size of <0.5 micrometers. In some embodiments, the cured body has a peel strength of about 3-10 lb / in on 1 ounce LP copper. In some embodiments, the cured body has a peel strength of about 2.2-5 lb / in on 1 ounce ANP copper. In some embodiments, the cured body has a peel strength of about 4-10.5 lb / in on 1 ounce "shiny" copper. In some other embodiments, the cured body has a peel strength of about 2.9-9 lb / in on 1 ounce VLP copper. In some other embodiments, the cured body has a peel strength of about 2.6-8.5 lb / in on 1 ounce HVLP copper.
[0151] The Young's modulus of the curable film or the cured body obtained from curing the curable film ranges from about 0.01 GPa to about 10 GPa, preferably 0.01 GPa to 6 GPa, more preferably 0.01 GPa to 2 GPa, and even more preferably 0.01 GPa to 1 GPa. In some embodiments, the Young's modulus of the cured body is about 0.05 GPa, 0.1 GPa, 0.15 GPa, 0.2 GPa, 0.25 GPa, 0.3 GPa, 0.35 GPa, 0.4 GPa, or 0.45 GPa. In some embodiments, the Young's modulus of the cured body is about 0.5 GPa, 0.55 GPa, 0.6 GPa, 0.65 GPa, 0.7 GPa, 0.75 GPa, 0.8 GPa, 0.85 GPa, 0.9 GPa, or 0.95 GPa. In some embodiments, the Young's modulus of the cured body is about 1 GPa to about 2 GPa. In some embodiments, the Young's modulus of the cured body is about 2 GPa to about 3 GPa. In some embodiments, the Young's modulus of the cured body is about 3 GPa to about 4 GPa. In some embodiments, the Young's modulus of the cured body is about 4 GPa to about 10 GPa.
[0152] The glass transition temperature (Tg) of the cured body resulting from curing the curable film may range from about -75°C to about 200°C as determined by thermomechanical analysis (TMA). Preferably, the cured body has a Tg of approximately -75°C to 150°C as determined by TMA. In some embodiments, the Tg of the cured body ranges from about -75°C to about 30°C as determined by TMA. In some embodiments, the Tg of the cured body ranges from about 0°C to about 150°C as determined by TMA. In some other embodiments, the Tg of the cured body ranges from about 0°C to about 100°C as determined by TMA.
[0153] In some embodiments, the cured body resulting from curing the curable film has a thermal conductivity of greater than 0.3 W / mk. In some embodiments, both the curable film and the cured body resulting from curing the curable film have a substantially isotropic coefficient of thermal expansion (CTE) when unclad. The cured body may have an average CTE ranging from about 10 to 400 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured body has an average CTE of about 10 to 35 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured body has an average CTE of about 10 to 60 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured body has an average CTE of about 60 to 100 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured body has an average CTE of about 100 to 200 ppm / °C in a temperature range of 25°C to 260°C. In some embodiments, the cured body has an average CTE of about 100-150 ppm / ° C. in the temperature range of 25° C. to 260° C. In some other embodiments, the cured body has an average CTE of about 150-250 ppm / ° C. in the temperature range of 25° C. to 260° C.
[0154] In some embodiments, the cured body resulting from curing the curable film has a dielectric constant (Dk) measured at 10 GHz of less than 3.5, preferably about 1.7 to about 3.2. In some embodiments, the cured body has a Dk measured at 10 GHz of about 2.5 to 3.2. In some embodiments, the cured body has a Dk measured at 10 GHz of about 2.85 to 3.2. In some embodiments, the cured body has a Dk measured at 10 GHz of less than about 2.45. In some embodiments, the cured body has a Dk measured at 10 GHz of about 1.7 to 2.2. In some other embodiments, the cured body has a Dk measured at 10 GHz of about 1.8 to 2.45.
[0155] In some embodiments, the cured body obtained from curing the curable film has a dissipation factor (Df) measured at 10 GHz of less than 0.005. In some embodiments, the cured body has a Df measured at 10 GHz of about 0.004, 0.0035, 0.0033, 0.0030, 0.0028, 0.0026, or 0.0025. In some embodiments, the cured body has a Df measured at 10 GHz of about 0.0024 to about 0.0020. In some embodiments, the cured body has a Df measured at 10 GHz of about 0.0020 to about 0.0008. In some embodiments, the cured body has a Df measured at 10 GHz of about 0.0018 to about 0.0008. In some embodiments, the cured body has a Df measured at 10 GHz of about 0.0015 to about 0.0008. In some other embodiments, the cured body has a Df measured at 10 GHz of about 0.0014 to about 0.0008.
[0156] Printed Circuit Board (PCB) Also provided is a PCB that includes one or more dielectric layers derived from the curable films described herein.
[0157] There are two main failure modes for vias in PCBs: (1) overstress and (2) low cycle fatigue. Overstress can be manifested during the reflow process where the assembly temperature is typically around 250°C. Multiple passes are typically required for reflow and the combination of overstress and cycle fatigue can cause microvia failure. The second failure mode is low cycle fatigue (less than 1,000 to 10,000 cycles) caused by operating conditions that can range between -55°C to 135°C in extreme cases. In both failure modes, the key driver of poor reliability is believed to be the difference in coefficient of thermal expansion (CTE) between the metal (typically copper) conductor and the material used for the dielectric layer. Failure due to idiosyncratic thermo-mechanical properties of the constituent materials of the PCB or IC board package can be manifested in a number of ways, including cracks in the copper interconnects (i.e., in plated through holes and vias) and voids from delamination. All these failure modes stem from stresses applied to the interconnects resulting from the thermo-mechanical strain mismatch between the copper conductive layers and the dielectric insulating layers.
[0158] It has been widely taught for decades in the art of PCB design and PCB material science, accepted as a core teaching of the prior art, and known to those skilled in the art, that PCB reliability can only be achieved if the PCB is constructed from a dielectric base material with the lowest possible CTE, aimed at matching the CTE of copper (approximately 17 ppm / °C) throughout the temperature range from ambient temperature to reflow or assembly temperature (typically around 250-260°C). Similarly, it has also been taught and accepted as basic knowledge by those skilled in the art that a higher Young's modulus (i.e., a more rigid material) is also required to minimize the thermomechanical stresses that arise between the copper conductive layer and the adjacent dielectric layer during the PCB manufacturing process and throughout the life cycle of the PCB product. Since CTE and Young's modulus are interrelated, PCB base materials that result in a low CTE also have a relatively high Young's modulus. The requirement that suitable PCB base materials require a low CTE close to or matching the CTE of copper and a high Young's modulus to minimize mechanical stress induced by CTE mismatch during the manufacturing, processing, and life cycle required for PCBs is a fundamental, deep-rooted, and unshakable teaching since the beginning of the PCB industry. Dielectric materials suitable for use in PCB assemblies are thus required to have a low CTE as close as possible to the CTE of copper to minimize mechanical stress induced by mismatch expansion, a high modulus of elasticity to resist mechanical stress induced by thermal expansion, and a high glass transition temperature (Tg) to ensure that the dielectric material can withstand the PCB manufacturing process and the subsequent device life cycle without catastrophic failure induced by the sudden change in thermo-mechanical properties occurring above Tg. These are the basic teachings of PCB material design, the core of the knowledge base of those skilled in the art, and the inviolable design rules for the selection and development of suitable PCB dielectric materials. These rules are especially important for HDI PCB construction, where the internal connections between the conductive layers of the PCB are much more fragile and much more susceptible to destruction during manufacturing and throughout the HDI PCB lifecycle.The fragility of these interconnects, called microvias, has led to further limitations on acceptable dielectric materials and more restrictive design rules for HDI PCBs. For example, prior to the present invention, it was well known to those skilled in the art that PCB designs using stacked microvias located directly above buried microvias were not adequately reliable and should be avoided. Similarly, multi-layer HDI PCBs having more than 2-4 layers cannot be reliably produced with any previously known dielectric materials that will withstand both the manufacturing and post-manufacturing thermal cycling test conditions.
[0159] In contrast to this known body of knowledge, the inventors have discovered that, although in some embodiments the dielectric layers of the present invention have low Tg, low modulus, and / or high CTE, such dielectric layers may surprisingly be suitable for use in the manufacture of reliable PCBs. Even more surprisingly, the inventors have found that previously unattainable PCB structures may actually be manufactured by using the dielectric materials of the present invention, which are designed and manufactured in stark opposition to conventionally accepted dielectric material design requirements. That is, contrary to conventional teachings in PCB material design, reliable PCBs may be constructed from dielectric materials having thermo-mechanical properties outside conventionally accepted property limits. The dielectric layers of the present invention have been found to be particularly useful in manufacturing multi-layer PCBs and HDI PCBs, which achieve higher reliability and allow for increased interconnection density. In some embodiments of the present invention, the dielectric layers enable the use of stacked vias, which can withstand assembly and have long fatigue lives under operating conditions. In one particularly surprising example, an embodiment of the present invention was used to generate an HDI PCB structure having four layers of stacked microvias stacked directly above buried vias. HDI PCBs constructed according to embodiments of the present invention survived preconditioning for manufacturing with 6x reflow at 260°C. The same HDI PCB structure then survived over 100 thermal stress cycles between room temperature and 160°C without failure of the interconnects between the conductive layers. Such highly complex arrangements of stacked multi-layer microvias directly above and above buried microvias cannot be reliably achieved with any other conventional PCB dielectric material. No currently available dielectric material can be reliably incorporated into multi-layer HDI PCB structures of more than four layers without experiencing substantial failure of the conductive layer interconnects during preconditioning, manufacturing, and post-manufacturing thermal cycling as described above.
[0160] The properties that make the dielectric layer of the present invention ideal for PCBs, particularly multi-layer PCBs and HDI PCBs, include low Dk and / or low Df and / or low skew in combinations previously unattainable in dielectric layers configured as base layers in PCBs, the ability to reach dielectric thicknesses below 50 μm, improved dielectric spacing, enhanced adhesion to materials including metals such as copper, increased microvia reliability, and lower insertion loss (e.g., <0.0012, <0.0015, <0.002, or <0.003) due to a combination of very low Dk and low Df. In addition, because the dielectric layer of the present invention is a homogenous, isotropic film, weave effects can be eliminated that particularly plague woven fabric reinforced composites and cause skew or timing problems in high speed digital transmission across PCBs.
[0161] In addition to chip packaging, standard double and single sided boards, motherboards, sequential lamination boards, multi-layer and standard layer count boards, and flexible boards, HDI PCBs used for IoT devices, camera modules, infotainment systems, mobile phones, tablets, and other consumer devices will greatly benefit from the use of this new material. Additionally, potential improvements in laser processability and increased throughput due to the absence of glass fibers, the ability to break through the dielectric thickness barrier, potential 20-30% thickness reduction in the board, lighter weight PCBs, ability to reduce stress on copper plated vias, reduced Z expansion which increases microvia reliability, and improved crack resistance due to thickness control are some additional benefits that can be expected from the new material of the present invention.
[0162] Having generally described the invention, a further understanding can be obtained by reference to certain specific examples, which are provided below for purposes of illustration only and are not intended to be limiting. EXAMPLES
[0163] [Preparation of curable film] The curable film examples were generally prepared by mixing and uniformly dispersing the components of the curable film composition (see Tables 1 and 2 for the various curable film compositions of the comparative and inventive examples described herein) in a suitable solvent (toluene, or ethyl acetate, or 1,3 dioxalane, or any mixture thereof) in a high speed rotating mixer to produce a varnish, followed by bar coating the varnish onto a carrier film to obtain an assembly, and then oven drying the assembly to a retained solvent level of <1%. Depending on the height of the bar, curable films having thicknesses of about 0.5 to 4 mils could be obtained.
[0164] To prepare the curable film for PCB, a varnish was first prepared by mixing and dispersing the components of the curable film composition in a suitable solvent (toluene, or ethyl acetate, or 1,3 dioxalane, or any mixture thereof) using a Cowles mixer or high viscosity propeller. The solvent also serves to adjust the viscosity of the final varnish to approximately 2,700 centipoise (cps) at 22°C. The varnish composition was then continuously coated by a die coater onto a 26 inch wide, 2 mil thick PET-based carrier film to create an assembly. The resulting assembly was then passed through a four-zone dryer. The line speed and zone temperatures of the dryer were adjusted to ensure that the residual solvent level in the product was about 1% or less. The product was wound into rolls and / or flattened to dimensions of 18 inches by 24 inches. This procedure was specifically used to produce dielectric curable films on carriers having thicknesses of 3.5 mil, 2 mil, 1.2 mil, or 1.0 mil, but may be adjusted to produce other curable films.
[0165] For property testing purposes, layers of the curable films were stacked together to build up thickness for electrical and thermomechanical testing and consolidated by curing at temperatures between 160 and 250°C for approximately 1 to 4 hours using a hydraulic platen press. The dielectric constant (Dk) and dissipation factor (Df) at 10 GHz were obtained using a split post dielectric resonator. The coefficient of thermal expansion (CTE (ppm / °C)) was obtained using a thermomechanical analyzer (TMA) according to IPC-TM-650 2.4.24.5. Young's modulus was measured at 30°C using a dynamic mechanical analyzer (DMA). The glass transition temperature (Tg (°C)) was obtained using a TMA. The peel strength values (lb / in) presented in Table 1 were measured using 1 oz. standard HTE "shiny" copper foil and the peel strength values (lb / in) presented in Table 2 were measured using 1 oz. HVLP copper foil.
[0166] E1-E13 shown in Table 1 were inventive examples that contained HGM and diene rubber ("DR") as essential components of the curable film composition. Some of these examples also contained liquid rubber ("LR"). C1-C5 were comparative examples. The weight percent of HGM, DR, or LR for each example listed in the table was calculated based on the total weight of the curable film. Other curable film ingredients as described in this disclosure made up the balance.
[0167] The inventive curable films E1-E13 were all Type-5 films. They were tack-free to the touch and had sufficient plastic-like quality that they could be easily peeled from the disposable PET-based carrier and handled in a free-standing form. The cured bodies of the curable films E1-E13 all had low Df and very low or extremely low Dk. In addition, the cured bodies of the curable films E1-E13 had Young's moduli ranging from about 0.1 GPa to 1.4 GPa, and average CTEs in the temperature range of 25-260°C from about 26 ppm / °C to <310 ppm / °C. Thus, as shown by these examples, a wide range of mechanical, thermal, and electrical properties suitable as PCB dielectric materials can be achieved by the specific combination of HGM, diene rubber, and other components in the rubber composition (B) of the inventive curable films described herein.
[0168] [Table 1]
[0169] Comparative Example C1 did not contain HGM or any other fillers. A Type-5 curable film was obtained, and although the cured product had sufficiently good dielectric properties (low Dk of 2.48 and low Df of 0.0018), it failed the PCB reliability test described below, and thus was not suitable for use in the construction of rigid PCBs or as a build-up layer for making HDI PCBs.
[0170] Comparative Examples C2 and C3 did not contain enough HGM and the cured bodies had CTE values above 310 ppm / ° C. As with Comparative Example C1, the cured bodies could not be used as reliable PCBs because they could not withstand even a single heat press cycle required for preconditioning or fabrication of PCBs, nor could they withstand post-fabrication thermal stress cycles.
[0171] As shown by Comparative Examples C4 and C5, when the amount of HGM in the curable film was too high (greater than 70 wt%), a substantially uniform and homogeneous curable film could be formed on the carrier, but it was only a Type-2 film because it was not transferable or releasable and could not be removed in its entirety from the carrier. In fact, the curable films of C4 and C5 were brittle and crumbled.
[0172] E14-E26 shown in Table 2 were inventive examples that contained filler (HGM and / or fused silica), diene rubber, and grease-maleimide resin (GMR) as essential components of the curable film composition. The weight percent of filler, diene rubber, or GMR was calculated based on the total weight of the curable film. Other curable film components as described in this disclosure made up the balance.
[0173] As shown in Table 2, the inventive curable films E14-E26 were all Type-5 curable films with excellent electrical properties and excellent peel strength even when measured using less rough copper foil. These examples showed that Type-5 films could still be obtained even with high filler loadings of HGM and / or silica (e.g., >65 wt%). Example E16, for example, showed that a Df of <0.001 was achievable when the curable film also contained an extremely low Df hydrocarbon polymer or elastomer, such as a cyclic olefin copolymer-based elastomer. Table 2 shows that the combination of DR, GMR, HGM, and silica can be adjusted to tailor the Dk and / or Df properties, resulting in any Dk between about 1.8 and about 3.2.
[0174] [Table 2]
[0175] [Manufacturing of multi-layer PCBs] A 20-layer hybrid PCB using a curable film instead of prepreg layers as a bonding layer between copper foils was built with the basic stack-up structure detailed in Figure 2. The PCB was constructed using 5.0 mil standard FR4 (fiberglass reinforced dielectric) material, 1.0 oz copper foil as the inner copper layer, and a curable film each with a thickness of about 3.5 mils. The curable film was used as a bonding layer instead of the commonly used glass reinforced prepreg layers. The PCB panel had a typical panel size dimension of 18 inches by 24 inches for mass production. Each inner copper layer was chemically etched to create the desired copper features and then chemically treated using standard PCB processes to prepare the copper surface for lamination.
[0176] The PCB was laminated in a vacuum press under predefined conditions suitable for curing the curable film. Typically, the materials were exposed to full vacuum throughout the entire press cycle, reaching a temperature of about 210° C., under pressures of up to 400 PSI for a total time of about 3 hours.
[0177] The 20-layer hybrid PCB was then mechanically drilled, the holes were cleaned and plated, the outer circuitry was etched, and the PCB was finished with solder mask. The individual PCB boards were then routed to yield the finished board. Sections were taken from the finished PCBs and subjected to thermal stress and evaluated in accordance with IPC-TM-650 2.6.8.
[0178] <Multilayer PCB of the invention> In this example, the curable film E9 in Table 1 was used as the curable film in the 20-layer hybrid PCB. As shown in Figure 3, the PCB passed the thermal stress test with no voids or other signs of thermal stress.
[0179] <Comparison multilayer PCB> In this comparative example, the curable film C1 in Table 1 was used as the curable film in the 20-layer hybrid PCB. As shown in Figure 4, the PCB failed the thermal stress test because voids appeared after thermal stress in the middle layer derived from the curable film C1, which did not contain HGM or silica filler.
[0180] [Manufacturing of multi-layer HDI PCB] A 4+6+4 HDI PCB with microvias offset from stacked buried via holes was fabricated by a lamination process. The detailed stackup structure is shown in Figure 5. The center layer was glass reinforced high Tg FR4 material. Also, in this example, four layers of curable film E9 from Table 1, each with a thickness of about 3.5 mils, were added on both sides of the center by a sequential lamination process. The HDI PCB was fabricated in a similar manner to the multilayer PCB described above, except that laser processing was used to form the microvia cavities.
[0181] The type of microvia structure in which a microvia is fabricated directly above a buried via is known as "unreliable" because it is particularly vulnerable to thermal breakdown during manufacturing and thermal stress testing. Thus, such designs are taught contrary to and not accepted by PCB industry groups, including IPC and HDP, because there are no suitable conventional dielectric materials that can be incorporated into multilayer HDI PCBs that use this type of design. However, if these stacked-on-buried arrangements could be reliably incorporated into multilayer HDI PCBs, there is a need within the industry for such structures, as they would enable new kinds of multilayer HDI PCB architectures.
[0182] As highlighted in the optical cross section shown in FIG. 6 and the electrical test results shown in FIGS. 7A and 7B, the 4+6+4 HDI PCB of this example successfully passed standard industry testing for evaluation of HDI PCB reliability. HDI PCBs constructed using the curable films of the present invention passed stringent microvia accelerated testing consisting of 6 preconditioning cycles with reflow at 260° C., and also passed post-fabrication thermal reliability criteria with over 100 thermal stress cycles from room temperature to 160° C. while constantly monitoring the electrical resistance of the structure. In particular, all variations such as microvias directly above the buried via hole, or microvias slightly offset from the centerline of the buried via hole, e.g., by about 3.0 mils to 8.0 mils, but still above the buried via, met the IPC-TM-650 method 2.6.7.2 requirement of 5% maximum resistance change, as shown in FIGS. 7A and 7B.
[0183] The detailed description of the invention set forth above provides methods and processes for making and using the same to enable any person skilled in the relevant art to make and use the same, and this enablement is provided particularly for the subject matter of the appended claims, which form a part of the original specification. This specification is provided in the context of a particular application and its requirements. Various modifications to the embodiments will be readily apparent to those skilled in the relevant art, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the invention. Thus, the present invention is not intended to be limited to the embodiments shown, but is to be accorded the widest scope consistent with the principles and features disclosed herein. In this regard, certain embodiments within the invention may not show all the benefits of the invention because they are broadly considered.
Claims
1. (A) hollow glass microspheres having a D50 of 19.5 μm or less; (B) a rubber composition containing at least one diene-based rubber, A curable film having a content of hollow glass microspheres ranging from 2% by weight to 65% by weight based on the total weight of the curable film, the thickness of the curable film is 105 μm or less, and A curable film, wherein the cured film obtained from the curable film has an average coefficient of thermal expansion greater than or equal to 60 ppm / °C in the temperature range of 25°C to 260°C.
2. the at least one diene-based rubber in the rubber composition has a weight average molecular weight of 60,000 or greater; 10. The curable film of claim 1, wherein the rubber composition further comprises at least one liquid rubber having a weight average molecular weight of 55,000 or less.
3. The curable film of claim 1 , wherein the rubber composition further comprises at least one poly(arylene ether).
4. The curable film of claim 1 , wherein the rubber composition further comprises one or more initiators and / or curing agents.
5. The curable film of claim 1 , wherein the rubber composition further comprises one or more flame retardants.
6. 10. The curable film of claim 1, having a service life of greater than 90 days at ambient temperature without humidity control, during which the rheological, electrical, and thermomechanical properties of the curable film remain unchanged.
7. A cured film obtained by curing the curable film according to claim 1.
8. 8. The cured film of claim 7 having a dielectric constant at 10 GHz of 3.5 or less.
9. A printed circuit board comprising a dielectric layer obtained by curing the curable film of claim 1.
10. An interconnect package comprising the curable film of claim 1.
11. An interconnect package comprising the cured film of claim 7.
12. (A) hollow glass microspheres having a D50 of 19.5 μm or less; (B) a rubber composition containing at least one diene-based rubber, A curable film having a content of hollow glass microspheres ranging from 2% by weight to 65% by weight based on the total weight of the curable film, the curable film does not contain fiberglass or woven reinforcing materials; and A curable film, wherein the cured film obtained from the curable film has an average coefficient of thermal expansion greater than or equal to 60 ppm / °C in the temperature range of 25°C to 260°C.
13. the at least one diene-based rubber in the rubber composition has a weight average molecular weight of 60,000 or greater; 13. The curable film of claim 12, wherein the rubber composition further comprises at least one liquid rubber having a weight average molecular weight of 55,000 or less.
14. The curable film of claim 12 , wherein the rubber composition further comprises at least one poly(arylene ether).
15. 13. The curable film of claim 12, wherein the rubber composition further comprises one or more initiators and / or curing agents.
16. 13. The curable film of claim 12, wherein the rubber composition further comprises one or more flame retardants.
17. 13. The curable film of claim 12, having a service life of greater than 90 days at ambient temperature without humidity control, during which the rheological, electrical, and thermomechanical properties of the curable film remain unchanged.
18. A cured film obtained by curing the curable film according to claim 12.
19. 20. The cured film of claim 18 having a dielectric constant at 10 GHz of 3.5 or less.
20. A printed circuit board comprising a dielectric layer obtained by curing the curable film of claim 12.
21. 13. An interconnect package comprising the curable film of claim 12.
22. 20. An interconnect package comprising the cured film of claim 18.
Citation Information
Patent Citations
Low-density fiber reinforced composite material product and preparation method thereof
CN114714679A
High-damping sound-absorbing high-tensile-strength light rubber and preparation method thereof
CN115594899A
Resin composition, prepreg, resin-attached film, resin-attached metal foil, metal-cladded laminate sheet, and printed wiring board
WO2020121734A1